Heating device to prevent or remove deposits
By applying photothermal elements containing transition metals on the surface, the photothermal effect absorbs near-infrared electromagnetic radiation, the problem that traditional technology is difficult to prevent condensation for a long time is solved, and efficient anti-fog and anti-freeze effects are achieved, while maintaining visible light transparency.
Patent Information
- Application Number
- JP2024554928
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-14
- Filing Date
- 2023-03-14
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively prevent or remove surface condensation in the long run, resulting in blurred vision, especially in high humidity environments, where traditional superhydrophobic surfaces tend to lose their robustness and expansion.
Photothermal elements containing transition metals are used that have the photothermal effect of transition metals and perform photothermal conversion when receiving near-infrared photoelectromagnetic radiation, thereby generating heat to prevent condensation.
It is achieved that the near-infrared electromagnetic radiation is strongly absorbed without affecting the transparency of visible light, and the surface temperature is increased to prevent condensation and freezing, which significantly improves the clarity of the field of view and anti-fog performance.
Smart Images

Figure 2025509647000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a heating device for preventing or removing deposits, in particular for condensation removal such as defogging, condensation prevention such as fog prevention, ice removal or ice prevention, and to a method for manufacturing such a heating device. [Background technology]
[0002] Loss of transparency and visibility due to condensation, i.e. fogging, on surfaces such as windows, windshields, prescription eyewear, sports eyewear, optical sensors, displays, and most recently, eyewear when wearing a mask, is disruptive and detrimental to many daily activities [Non-Patent Documents 1, 2]. Loss of transparency due to fogging is found in many social and industrial sectors such as medicine, security, energy / photovoltaics, and chemical / food [Non-Patent Document 3]. Fogging of surfaces usually occurs due to the nucleation of a large number of microdroplets on the surface as a result of a decrease in temperature or an increase in the ambient relative humidity [Non-Patent Documents 1, 4, 5]. These droplets scatter the incident light and thus adversely affect transparency and visibility [Non-Patent Documents 6-8]. To mitigate this phenomenon while maintaining transparency, different attempts have been designed and implemented, including passive and energy-neutral approaches, even beyond Joule heating. Temporary solutions such as superhydrophilic surfaces [6] or surfactants modify the surface energy, resulting in a nearly continuous, very thin layer of condensate. Thus, the scattering of incident light is reduced, and transparency to the human eye can be maintained [7-9]. However, this water film is not always uniform due to gravity, drying, and contaminants, which leads to distortions of visibility
[10] . Such surfaces are inherently susceptible to contamination from organic contaminants due to their high surface energy, which significantly limits the persistence of their effectiveness [1,11]. Typically, more long-lasting passive solutions rely on micro- and nano-patterned superhydrophobic surfaces [12-15], aiming to self-clean condensed water droplets on the surface at a very early stage, before they can grow to a size that would have a significant impact on transparency [16,17]. Due to the low surface energy of these surfaces and the texture of these surfaces, the condensed droplets maintain high mobility (Cassie-Baxter wetting state
[18] ) and avoid pinning of the droplets on the surface (Wenzel wetting state
[19] ).However, when exposed to high relative humidity environments, very complex engineering of the structures (not easily robust and not easily extendable to glass) is required, because nanoscale nucleation within the textures annihilates the Cassie-Baxter state and induces the Wenzel state, destroying their superhydrophobic properties
[20] . Thus, the previously mentioned approaches are insufficient as long-term passive solutions to completely eliminate haze formation while maintaining high visibility, and new solutions are highly desirable and required.
[0003] A recent alternative approach to thwart fogging is to exploit the abundant natural energy of the sun in combination with its selective and efficient absorption in combination with the nucleation thermodynamics of condensates. The absorbed sunlight can be dissipated as heat (photothermal effect), which itself reduces the chances of nucleation occurring or (if already covered by fogging) quickly dries the surface and restores its transparency. Previous work has focused on fabricating sunlight-absorbing surfaces from carbon-based materials [Non-Patent Documents 21, 22], plasmonic metal inclusions [Non-Patent Documents 10, 23-25], polymers [Non-Patent Documents 26, 27], or multilayer selective absorbers [Non-Patent Documents 28]. However, these surfaces are designed to be broadband absorbing [Non-Patent Documents 10, 17, 29-33] and usually must compromise either transparency or heating depending on the main effect targeted. Interestingly, about half of the solar energy is in the near-infrared spectrum, which is invisible to the human eye. This physical fact can be exploited to design spectrally selective coatings that are transparent in the visible range and sufficiently absorbing in the infrared range of the solar spectrum to cause photothermal heating. Such attempts have hardly been demonstrated in practice. Moreover, such coatings are either narrow-band absorbing [34, 35] or thick [24, 36] (several μm and rather cumbersome to manufacture) to achieve the required temperature increase, and are therefore difficult to integrate into existing processes for many of the applications mentioned above. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Yoon, J. et al. Wet-Style Superhydrophobic Antifogging Coatings for Optical Sensors. Advanced materials (Deerfield Beach, Fla.) 32, e2002710; 10.1002 / adma.202002710 (2020). [Non-Patent Document 2] Howarter, JA & Youngblood, JP Self-Cleaning and Next Generation Anti-Fog Surfaces and Coatings. Macromol. Rapid Commun. 29, 455-466; 10.1002 / marc.200700733 (2008). [Non-Patent Document 3] Duran, IR & Laroche, G. Current trends, challenges, and perspectives of anti-fogging technology: Surface and material design, fabrication strategies, and beyond. Progress in Materials Science 99, 106-186; 10.1016 / j.pmatsci.2018.09.001 (2019). [Non-Patent Document 4] Leach, R. N., Stevens, F., Langford, S. C. & Dickinson, J. T. Dropwise condensation: experiments and simulations of nucleation and growth of water drops in a cooling system. Langmuir: the ACS journal of surfaces and colloids 22, 8864-8872; 10.1021 / la061901 (2006). [Non-Patent Document 5] Sun, X., Hong, R., Hou, H., Fan, Z. & Shao, J. Thickness dependence of structure and optical properties of silver films deposited by magnetron sputtering. Thin Solid Films 515, 6962-6966; 10.1016 / j.tsf.2007.02.017 (2007). [Non-Patent Document 6] Lin, S. et al. Stretchable Anti-Fogging Tapes for Diverse Transparent Materials. Adv. Funct. Mater. 31, 2103551; 10.1002 / adfm.202103551 (2021). [Non-Patent Document 7] Cebeci, F. C., Wu, Z., Zhai, L., Cohen, R. E. & Rubner, M. F. Nanoporosity-driven superhydrophilicity: a means to create multifunctional antifogging coatings. Langmuir: the ACS journal of surfaces and colloids 22, 2856-2862; 10.1021 / la053182p (2006). [Non-Patent Document 8] Tzianou, M., Thomopoulos, G., Vourdas, N., Ellinas, K. & Gogolides, E. Tailoring Wetting Properties at Extremes States to Obtain Antifogging Functionality. Adv. Funct. Mater. 31, 2006687; 10.1002 / adfm.202006687 (2021).
Non-Patent Document 9
Non-Patent Document 10
Non-Patent Document 11
Non-Patent Document 12
Non-licensed Document 13
Non-licensed Document 14
Non-licensed Document 15
Non-licensed Document 16
Non-licensed Document 17
Non-licensed Document 22
Non-licensed Document 23
Non-licensed Document 24
Non-licensed Document 25
Non-licensed Document 26
Non-Patent Document 31
Non-Patent Document 32
Non-Patent Document 33
Non-Patent Document 34
[0005] It is an object of the present invention to provide an improved heating device for preventing or removing buildup, in particular for condensation removal, dew prevention, ice removal or ice prevention.
[0006] The above object is achieved by a heating device according to claim 1. A heating device is provided for preventing or removing deposits, in particular for condensation removal such as defogging, condensation prevention such as fog prevention, ice removal or ice prevention. The heating device extends along an extension direction and comprises at least one photothermal element configured to exhibit a photothermal effect when electromagnetic radiation is incident on it. The photothermal element comprises or consists of a photothermal material comprising a percolation structure. The percolation structure is at or substantially at its percolation threshold.
[0007] The heating device according to the invention is therefore configured to generate heat upon incidence of electromagnetic radiation on the photothermal element, in other words the photothermal element is configured to perform a photothermal conversion of the electromagnetic radiation, the photothermal element absorbing the electromagnetic radiation and dissipating this electromagnetic radiation as heat, thereby increasing the temperature of the heating device.
[0008] As will be explained in more detail below with respect to the method for producing such a heating device, the photothermal element is preferably produced by chemical growth and / or deposition of material on a substrate, which is preferably a dielectric element, a shift element or a carrier element. For this purpose, the photothermal element is produced by island growth, in the case of deposition, in a first step, discrete islands of the deposited material are formed, said discrete islands growing progressively during the further course of the deposition. For this purpose, it is particularly preferred to produce the photothermal element according to the so-called Volmer-Weber growth method, which is well known in the art (see, for example, https: / / link.springer.com / content / pdf / 10.1007%2F978-981-10-6884-3.pdf). In the Volmer-Weber (VW) growth process, small islands nucleate on the substrate during the initial stages of growth, followed by growth and collision of the islands to form a continuous layer. This growth mode prevails when the bond strength between the layer atoms is stronger than the bond between the layer atoms and the substrate atoms. The layer atoms tend to stay closer to similar atoms than to the substrate atoms, so small islands form at the beginning of growth. When the islands collide with each other, grain boundaries form and the film microstructure is therefore polycrystalline (assuming no epitaxial relationship with the substrate has been established).
[0009] After a certain amount of conductive material is deposited, the individual islands contact each other and form the conductive patterns or pathways mentioned above, i.e., the percolation structure.
[0010] Finally, a randomly distributed photothermal material is generated, said photothermal material forming a random conductive pattern or a random conductive path. Since the photothermal material is preferably generated on a substrate, the photothermal material is preferably randomly distributed on said substrate so as to form a completely random conductive pattern or a conductive path on the substrate. In other words, it can be said that the photothermal elements are randomly arranged on the substrate.
[0011] The percolation threshold is where the photothermal material suddenly changes from an electrical insulator to a conductor due to the formation of a conductive pattern or pathway. In other words, percolation can be said to start at the percolation threshold, and exists when a conductive pattern or pathway is formed and electrons or current can flow. The presence or absence of such a conductive pattern or pathway may be examined by measuring the electrical conductivity of the photothermal material, or by, for example, electron or scanning electron microscopy, where the connectivity of the pathways is visually observed and quantified.
[0012] The photothermal element preferably exhibits electrical resistance. Electrical resistance in the presence of electron flow is associated with the most random state of the percolation structure and is therefore highest at the onset of percolation. The dielectric function of the photothermal structure diverges at the percolation threshold and is characterized by both DC (direct current, i.e. low frequency) conductivity and AC (alternating current, i.e. optical / high) frequency. At DC, it is characterized by a power law decrease in electrical resistance from high (open circuit) to low as the photothermal structure becomes more and more conductive with increasing thickness parameters of the photothermal structure.
[0013] This drop from high resistance to low resistance is understood herein as a power law decrease. Thus, the electrical resistance of a photothermal structure at or substantially at the percolation threshold preferably drops in a power law manner.
[0014] In the AC, i.e. in the optical region, a percolation structure that is substantially at the percolation threshold or even at the percolation threshold is further characterized by a broadband (i.e. almost wavelength independent, Kramers-Kronig relation) absorption spectrum, i.e. this broadband absorption is obtained above a certain wavelength that depends on the photothermal material, this certain wavelength will be referred to herein as the "minimum wavelength of the range of interest". The broadband absorption occurs between the minimum wavelength of the range of interest and the "maximum wavelength of the range of interest", e.g. up to 2500 nm for solar energy applications. A percolation structure that is substantially at the percolation threshold is understood to have a total absorption in the range of interest of at least 60% or more, preferably at least 70% or more, of the maximum total broadband absorption in the same range of interest.
[0015] For example, for a gold photothermal material substantially at the percolation threshold fabricated on a titanium dioxide dielectric element, the minimum wavelength of interest is about 800 nm. Alternatively, for a copper photothermal material substantially at the percolation threshold fabricated on a titanium dioxide dielectric element, the minimum wavelength of interest is about 800 nm, and for a silver photothermal material substantially at the percolation threshold fabricated on a titanium dioxide dielectric element, the minimum wavelength of interest is about 800 nm.
[0016] Depending on the photothermal material, the absorption behavior of percolation structures at or substantially at the percolation threshold may be the same.
[0017] Unless otherwise stated, "total absorbency" or "absorbency" in this specification is preferably understood as "average absorbency", i.e. as "average" absorbency without taking into account any weighting factors, such as, for example, sunlight.
[0018] As mentioned above, the percolation structure at the percolation threshold is preferably identified by measuring the electrical resistance of the photothermal material, where the electrical resistance shows a power law decrease. The electrical resistance of the photothermal material may be measured by a four-point probe measurement, such as the Jandel Universal Probe Station or any other probe station. For example, in the case of a gold photothermal material fabricated on a titanium dioxide dielectric element, the electrical resistance decreases from an open circuit (i.e., no conductive path exists) for a photothermal material thickness parameter of 4.25 nm (see below), to 400 ohms for a thickness parameter of 5 nm, and even to 107 ohms for a thickness parameter of 5.75 nm. At larger thickness parameters, the electrical resistance "flattens out". For example, the electrical resistance reaches a value of 5 ohms for a thickness parameter of 15 nm, and a value of 2 ohms for a thickness parameter of 30 nm.
[0019] In addition to the power law decrease in electrical resistance described above, a percolation structure substantially at its percolation threshold is preferably identified by measuring the absorption spectrum of the photothermal material, where the total absorbance within the range of interest is at least 60% or more, preferably at least 70% or more, of the maximum total broadband absorbance within the same range of interest, as described above.
[0020] The absorption spectrum of the photothermal material may be measured using a UV-VIS spectrometer (such as a Jasco, V770 equipped with an ILN-925 integrating sphere) or using a FTIR (such as a Nicolet Thermo Fisher Scientific).
[0021] For example, a percolation structure substantially at the percolation threshold, comprising a gold photothermal material on a titanium dioxide dielectric element, may exhibit an absorption, i.e., average absorption, of at least 17% of incident electromagnetic radiation within the region from 800 nm (the minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, e.g., to 2500 nm (i.e., the total absorption within the range of interest is at least 60% or more of the maximum total broadband absorption within the same range of interest). As another example, a percolation structure substantially at the percolation threshold comprising a copper photothermal material on a titanium dioxide dielectric element can exhibit an average absorption of at least 14% of incident electromagnetic radiation within the region from 800 nm (the minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, e.g., to 2500 nm (i.e., the total absorption within the range of interest is at least 60% or more of the maximum total broadband absorption within the same range of interest), and a percolation structure substantially at the percolation threshold comprising a silver photothermal material on a titanium dioxide dielectric element can exhibit an average absorption of at least 18% within the region from 800 nm (the minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, e.g., to 2500 nm (i.e., the total absorption within the range of interest is at least 60% or more of the maximum total broadband absorption within the same range of interest).
[0022] Depending on the photothermal material, for example in the case of a photothermal material made of gold on a dielectric element made of titanium dioxide, the absorption behavior of the percolation structure at the percolation threshold or substantially at the percolation threshold is the same. Additionally or alternatively, the expression "substantially at the percolation threshold" means that the percolation structure of the photothermal material constitutes a photothermal material that exhibits an absorption of more than 10%, for example more than 15%, more preferably more than 25%, particularly preferably more than 35%, in particular a total absorption, of incident electromagnetic radiation, preferably having a wavelength in the range of 700 nm to 2.5 μm, respectively.
[0023] For example, a percolation structure of photothermal material substantially at the percolation threshold, made of gold on a dielectric element made of titanium dioxide, constitutes a photothermal material that exhibits an average absorption of more than 17% of incident electromagnetic radiation in the region of 700 nm to 2.5 μm (i.e., the total absorption within the range of interest, here 700 nm to 2.5 μm, is at least 60% or more of the maximum total broadband absorption within the same range of interest, here 700 nm to 2.5 μm). As another example, a percolation structure of photothermal material substantially at the percolation threshold, made of copper on a dielectric element made of titanium dioxide, constitutes a photothermal material that exhibits an average absorption of more than 14% of incident electromagnetic radiation in the region of 700 nm to 2.5 μm (i.e., the total absorption within the range of interest, here 700 nm to 2.5 μm, is at least 60% or more of the maximum total broadband absorption within the same range of interest, here 700 nm to 2.5 μm). A percolation structure of the photothermal material, substantially at the percolation threshold, made of aluminum on a dielectric element made of titanium dioxide, constitutes a photothermal material that exhibits an average absorption of greater than 20% of incident electromagnetic radiation within the region of 700 nm to 2.5 μm (i.e., the total absorption within the range of interest, here 700 nm to 2.5 μm, is at least 60% or greater than the maximum total broadband absorption within the same range of interest, here 700 nm to 2.5 μm). The absorption spectrum of the photothermal material was measured using a UV-VIS spectrometer as previously described.
[0024] Additionally or alternatively, the expression "substantially at the percolation threshold" means that the percolation structure of the photothermal material is within 40%, e.g., within 30%, or within 20%, e.g., within 10%, or within 5% of the thickness parameter associated with the photothermal material exhibiting maximum overall broadband absorption between the minimum wavelength of the range of interest and the maximum wavelength of the range of interest, e.g., up to 2500 nm for solar energy applications. The thickness parameter is provided to a deposition device that produces the photothermal element by deposition (see further below). For this purpose, the deposition device corresponds to an Evatec BAK501 LL (thermal evaporator) or a Von Ardenne CS 320C (sputtering). The actual thickness of the deposited photothermal material may vary slightly from the tool-specific thickness parameter.
[0025] For example, if the percolation threshold of a photothermal material is 5 nm in thickness parameter, then the photothermal material substantially at the percolation threshold may be, for example, between 3.5 and 6.5 nm, preferably between 4 nm and 6 nm.
[0026] In particular, if the percolation threshold of a gold photothermal material on a titanium dioxide dielectric element is a thickness parameter of 4.75 nm, then the photothermal material substantially at the percolation threshold may be a thickness parameter between 2.9 and 6.7 nm (i.e., the percolation structure is within 40% of the thickness parameter associated with the photothermal material exhibiting the maximum overall broadband absorption in the range of interest), preferably between 3.3 and 6.2 nm (i.e., the percolation structure is within 30% of the thickness parameter associated with the photothermal material exhibiting the maximum overall broadband absorption in the range of interest). As another example, if the percolation threshold of a silver photothermal material on a titanium dioxide dielectric element is a thickness parameter of 7 nm, then the photothermal material substantially at the percolation threshold may be a thickness parameter between 4.2 and 9.8 nm, preferably between 4.9 and 9.1 nm. As another example, if the percolation threshold of a copper photothermal material on a titanium dioxide dielectric element is 5 nm in thickness parameter, the photothermal material substantially at the percolation threshold may be between 3 and 7 nm, preferably between 3.5 and 6.5 nm. As another example, if the percolation threshold of an aluminum photothermal material on a titanium dioxide dielectric element is 5 nm in thickness parameter, the photothermal material substantially at the percolation threshold may be between 3 and 7 nm, preferably between 3.5 and 6.5 nm. The thickness parameter is fed to a deposition device that produces the photothermal element by deposition. For this purpose, the deposition device corresponds to an Evatec BAK501 LL (thermal evaporator) or a Von Ardenne CS 320C (sputtering). The actual thickness of the deposited photothermal material may vary slightly from the tool-specific thickness parameter.
[0027] The photothermal material is preferably optically transparent, and more preferably is optically transparent to electromagnetic radiation in the visible region of the electromagnetic spectrum.
[0028] Additionally or alternatively, the photothermal material is preferably configured to absorb incident electromagnetic radiation, particularly preferably in the near infrared region of the electromagnetic spectrum.
[0029] The visible region (VIS) of the electromagnetic spectrum is understood to include electromagnetic radiation having wavelengths within the region of 300 nm to 720 nm, in other words, the photothermal material preferably exhibits broadband absorption in the NIR but not in the VIS.
[0030] The near infrared region (NIR) of the electromagnetic spectrum is understood to include electromagnetic radiation having wavelengths within the region of 720 nm to 2.5 μm.
[0031] The photothermal material is further configured to absorb 10% or more, for example 20% or more, or 30% or more, preferably 35% or more of the incident electromagnetic radiation in the near infrared region.The photothermal material further preferably has a transmittance of 40% or more, for example 50% or more, or 60% or more, preferably 65% or more in the visible region of the electromagnetic spectrum.Thus, the photothermal material is optically transparent, while being particularly preferably absorbing in the NIR.In fact, the photothermal material is particularly preferably strong broadband absorbing in the NIR, while being transparent in the VIS.
[0032] Furthermore, it should be noted that the transmittance of the photothermal material is independent or nearly independent of the angle of incidence at which the electromagnetic radiation is incident on the photothermal element due to the random distribution of the photothermal material.
[0033] Depending on the particular application of the heating device, the heating device is preferably designed to have significant absorption and transmission within a particular wavelength region or range of interest. For example, if the heating device is to be used with solar radiation, it is particularly preferred that the photothermal element is configured to strongly absorb electromagnetic radiation having a wavelength within the range of 720 nm to 1380 nm to match solar radiation, and is further configured to be optically transparent to electromagnetic radiation having a wavelength within the range of 450 nm to 650 nm. In this case, the photothermal element exhibits peak transparency at the wavelengths of solar radiation.
[0034] The photothermal elements may be electrically conductive or electrically insulating.
[0035] That is, the photothermal element may be electrically conductive, in which case the percolation structure of the photothermal material is at or above the percolation threshold, where above the percolation threshold means that the photothermal material is substantially at the percolation threshold as defined above, but at a higher value than the percolation threshold.
[0036] That is, if the percolation threshold of a photothermal material is, for example, 5, then a "percolation structure of a photothermal material that is above the percolation threshold" is greater than 5, for example 5.5.
[0037] However, it is equally contemplated that the photothermal element is electrically insulating, in which case the percolation structure of the photothermal material is below the percolation threshold. Below the percolation threshold means that the photothermal material is substantially at the percolation threshold as defined above, but at a lower value than the percolation threshold. That is, if the percolation threshold of the photothermal material is, for example, 5, then the "percolation structure of the photothermal material that is below the percolation threshold" is less than 5, for example, 4.5.
[0038] As mentioned above, percolation is related to the presence of conductive paths or conductive pattern paths that allow the transport of electrical energy. Electromagnetic radiation of certain wavelengths, such as electromagnetic radiation in the NIR, is related to electrical vibrations that propagate on the order of hundreds of nanometers. Thus, such electromagnetic radiation is not "localized" as precisely as electrons can be in photothermal materials. Thus, there may be cases where a photothermal element is not conductive but still allows the propagation of an oscillating field, preferably a high-frequency oscillating field, such as a NIR field. Thus, even if the percolation structure is not at the percolation threshold but is substantially at the percolation threshold, the heating device according to the invention is still able to generate heat (see above).
[0039] The heating device may further include at least one electrical element configured to induce an electrical current in the photothermal element, thereby causing heat to be generated by the photothermal element.
[0040] The heating device, which includes an electrical element, is preferably configured to generate heat by resistive heating, also known as Joule heating, i.e., an electrical current induced in the photothermal element is dissipated as heat within the percolation structure of the photothermal material.
[0041] The electrical elements are preferably electrodes, for example the edges of the percolation structure can be wired.
[0042] In the absence of electrical elements, the heating device can be said to be configured for wireless operation, i.e., the heating device is configured to generate heat solely through the photothermal material.
[0043] When an electrical element is present, the heating device can be said to be configured for wired operation, i.e., the heating device is configured to generate heat by the action of the photothermal material and the electrical element.
[0044] The electric element provides additional heat production in situations where the heat production by the photothermal material is insufficient, for example under adverse weather conditions or in the absence of light, for example at night, allowing the heating device to maintain its deposit removal function.
[0045] To this end, it is particularly preferred that the heating device comprises at least one electrical element when the photothermal material is at or above the percolation threshold as explained above.
[0046] That is, the heating device configured for wired operation preferably comprises a photothermal material at or above the percolation threshold, i.e. said photothermal material preferably corresponds to an electrical conductor, i.e. when configured for wired operation, the percolation structure substantially at the percolation threshold is preferably more than 40%, more preferably more than 30%, more preferably more than 20%, even more preferably more than 10%, particularly preferably more than 5% of the thickness parameter of the percolation threshold associated with the photothermal material.
[0047] The heating device configured for wireless operation preferably exhibits strong broadband absorption, and the photothermal material is preferably substantially at the percolation threshold and has a random ordering, with a maximum absorption substantially at the percolation threshold, i.e., when configured for wireless operation, the percolation structure substantially at the percolation threshold is preferably greater than or less than 40%, more preferably greater than or less than 30%, more preferably greater than or less than 20% of the percolation threshold thickness parameter associated with the photothermal material.
[0048] The photothermal element preferably has a thickness in the extension direction in the range of 1 nm to 50 nm, more preferably in the range of 1 nm to 10 nm, particularly preferably in the range of 4 nm to 8 nm, for example 5 nm.
[0049] Additionally or alternatively, the heating device preferably has a thickness in the range of 1 nm to 100 nm, more preferably in the range of 1 nm to 50 nm, particularly preferably in the range of 1 nm to 20 nm, for example 10 nm, in the extension direction. That is to say, the overall thickness of the heating device is preferably in the range of 1 nm to 100 nm, more preferably in the range of 1 nm to 50 nm, particularly preferably in the range of 1 nm to 20 nm, for example 10 nm, in the extension direction. However, larger thicknesses of the heating device are also conceivable, depending for example on the thickness of the substrate, such as the carrier element, used.
[0050] Additionally or alternatively, the photothermal element and / or the heating device has in each case a thickness, preferably in the extension direction, that is significantly smaller than the wavelengths in the visible and near infrared range of the incident electromagnetic radiation.
[0051] For example, the wavelength in the visible region of the electromagnetic spectrum is 450 nm. Therefore, the thickness of the photothermal element or heating device in the extension direction is smaller than 450 nm.
[0052] The heating device is preferably bendable. Additionally or alternatively, the heating device preferably includes an inverse curvature of greater than 1 μm when bent. Such an inverse curvature is related to the bending radius or curvature, and the scale of the random arrangement of the heating device is much smaller than the bending curvature radius, so that bending of the heating device does not affect the optical properties of the heating device.
[0053] The photothermal element is preferably a layer, said layer more preferably extending along a transverse direction extending perpendicular to the extension direction.
[0054] The photothermal material is preferably electrically conductive. Additionally or alternatively, the photothermal material preferably comprises or consists of at least one metal. For example, the photothermal material may comprise or consist of an elemental metal, such as, for example, gold, silver, aluminum, copper, platinum, or tungsten, or titanium. However, it is equally conceivable that the photothermal material comprises or consists of a metal alloy, such as, for example, PtAu, CuZn, CuAg, CuSn, AlCu, AgAlCu, or AgCu.
[0055] For this purpose, it is particularly preferred that the photothermal material corresponds to a metal layer, preferably even consisting of a single component. Considering the preferred thickness of the photothermal element outlined above, it can be said that the photothermal material corresponds to a thin metal layer. However, it is also preferred that the photothermal material is a semiconductor or a highly doped semiconductor, such as InAsSb, InAs, Ge, Si, GeSn. Semiconductors are preferably used when the heating device is aimed at the near infrared (NIR).
[0056] Additionally or alternatively, the photothermal material may comprise or consist of an optically transparent and electrically conductive oxide, so-called transparent conductive oxide (TCO), such as, for example, indium tin oxide (ITO). However, other transparent conductive oxides known in the art, such as antimony-doped tin oxide (ATO), indium tin oxide (ITO), indium zinc oxide (IZO), cadmium oxide (CdO), fluorine-doped tin oxide (FTO, SnO2:F), or aluminum-doped zinc oxide (AZO, ZnO:Al), are also contemplated. Additionally or alternatively, the photothermal material may comprise or consist of a transition metal nitride, in particular titanium nitride (TiN).
[0057] The photothermal material is preferably provided according to the end user's desired application of the heating device. For example, gold and copper are particularly suitable for absorbing the NIR, while silver and aluminum perform well in the VIS.
[0058] The heating device preferably further comprises at least one dielectric element, said dielectric element being arranged in front of or behind the light-heat element in the extension direction, i.e. the heating device preferably comprises at least one electrical insulator in the form of a dielectric element.
[0059] The dielectric element and the photothermal element can be in at least partial or full surface contact with each other, i.e. the dielectric element is preferably at least partially, particularly preferably fully, disposed on the surface of the photothermal element, in other words, the dielectric element and the photothermal element are preferably in surface contact with each other or in direct contact with each other.
[0060] The dielectric element is preferably optically transparent. Additionally or alternatively, the dielectric element preferably comprises at least one metal oxide, such as titanium dioxide (TiO2), silicon dioxide (SiO2), tantalum pentoxide (Ta2O5), or a metal nitride or metal carbide, such as silicon carbide (SiC) or titanium nitride (TiN), particularly preferably in the form of a continuous film, or preferably consists of at least one metal oxide, such as titanium dioxide (TiO2), silicon dioxide (SiO2), tantalum pentoxide (Ta2O5), or a metal nitride or metal carbide, such as silicon carbide (SiC) or titanium nitride (TiN).
[0061] The thickness of the dielectric element in the extension direction is preferably 1 nm or more, for example between 1 nm and 1 cm. More preferably, the thickness of the dielectric element is in the range of 1 nm to 5 nm, for example in the range of 1 nm to 3 nm.
[0062] It is further preferred that the dielectric element is at least partially functionalized. In fact, the dielectric element is preferably functionalized in the contact area with the photothermal element, such as the surface in surface contact with the photothermal element (see above). Said functionalization is preferably configured to influence the formation of percolation structures on the dielectric element. In fact, the functionalization preferably influences the growth of the percolation structures of the photothermal material, so that percolation structures at or substantially at the percolation threshold can be produced with thinner or thicker thickness parameters. The dielectric element is preferably functionalized so that its wettability is modified. For example, the dielectric element can be subjected to an ozone or oxygen plasma treatment, which causes oxygen groups to be attached to the surface of the dielectric element. As another example, the dielectric element may be functionalized with a single molecular layer. Of course, other functionalizations are equally conceivable and are known to the skilled person.
[0063] The heating device preferably comprises at least two dielectric elements, and the light-heat element is particularly preferably arranged between the two dielectric elements with respect to the extension direction. In other words, the light-heat element is preferably sandwiched between the two dielectric elements. The at least two dielectric elements may be the same as each other or may be different from each other. For example, both dielectric elements may be titanium dioxide or silicon dioxide. Alternatively, one dielectric material may be titanium dioxide and the other dielectric material may be silicon dioxide. It should be noted that many other dielectric materials are also conceivable.
[0064] The one or more dielectric elements are preferably layers, said layers preferably extending along a transverse direction extending perpendicularly to the extension direction.
[0065] That is to say, the heating device corresponds to a layered structure including one or more dielectric layers and at least one photothermal layer, preferably arranged one above the other in the extension direction.
[0066] The heating device may include two or more photothermal elements, preferably two or more photothermal layers, arranged one above the other in the extension direction, and these two or more photothermal elements are preferably further arranged at a distance from each other in the extension direction, for example a dielectric element may be arranged between these photothermal elements.
[0067] The heating device preferably further comprises at least one shift element, the shift element being configured to shift the absorption and / or transmission capability of the heating device with respect to incident electromagnetic radiation towards shorter or longer wavelengths of the incident electromagnetic radiation.
[0068] Shifting the absorption capability of the heating device towards longer (shorter) wavelengths means that the heating device is configured to absorb electromagnetic radiation of longer (shorter) wavelengths compared to not having a shifting element.Similarly, shifting the transmission capability of the heating device towards longer (shorter) wavelengths means that the heating device is configured to transmit electromagnetic radiation of longer (shorter) wavelengths compared to not having a shifting element.
[0069] The shift element particularly preferably results in a shift of the maximum average absorption or maximum total absorption and / or maximum average transmittance in the region of interest towards longer or shorter wavelengths.
[0070] As a result, the shift element serves the purpose of adjusting the absorption and / or transmittance of the heating device to the desired wavelength region of the electromagnetic spectrum. In fact, the shift element is configured to adjust the optical response (transmission and absorption) of the percolation structure of the photothermal material. For example, if the heating device is to be used with sunlight, it is preferable to shift the absorption capacity of the heating device, in particular its maximum average absorptance, to the peak wavelength region of solar radiation. Furthermore, if the heating device is required to be visually transparent, it is preferable to shift the transmission capacity of the heating device, in particular its maximum average transmittance, to the peak wavelength of the visible spectrum. In this case, it can be said that the shift element aligns the transparency peak of the heating device with the peak wavelength of solar radiation.
[0071] The shift element is preferably arranged before and / or after the photothermal element in the extending direction. For example, a percolation structure substantially at the percolation threshold, comprising a titanium dioxide dielectric element provided on the photothermal material and in at least partial or full surface contact with the photothermal material, and a gold photothermal material on the titanium dioxide shift element, can exhibit an average absorption of at least 19% of the incident electromagnetic radiation in the region from 1000 nm (the shifted minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, for example up to 2500 nm for solar energy applications. This indicates that the shift element shifts the minimum wavelength of the range of interest, i.e., the presence of the shift element results in a shifted minimum wavelength of the range of interest, and total absorption is obtained for wavelengths above the aforementioned shifted minimum wavelength of the range of interest. The shift element also preferably increases the maximum total absorption in the range of interest. As another example, a percolation structure substantially at the percolation threshold with a copper photothermal material on a titanium dioxide dielectric element and a titanium dioxide shift element disposed on the photothermal material and in at least partial or full surface contact with the photothermal material can exhibit an average absorption of at least 15% of incident electromagnetic radiation in the range from 820 nm (the shifted minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, for example, up to 2500 nm for solar energy applications. As another example, a percolation structure substantially at the percolation threshold with a silver photothermal material on a titanium dioxide dielectric element and a titanium dioxide shift element disposed on the photothermal material and in at least partial or full surface contact with the photothermal material can exhibit an average absorption of at least 17% of incident electromagnetic radiation in the range from 850 nm (the shifted minimum wavelength of the range of interest) to the maximum wavelength of the range of interest, for example, up to 2500 nm for solar energy applications.
[0072] The heating device is further preferably configured to absorb at least 15%, at least 25%, preferably at least 35% of the incident electromagnetic radiation in the near infrared range. For this purpose, the heating device comprises, for example, a photothermal element arranged in the extension direction between two dielectric elements, which preferably also correspond to shift elements at the same time (see also below). The aforementioned "dielectric shift element" may be, for example, titanium dioxide.
[0073] Additionally, the shifting element is preferably optically transparent and / or dielectric.
[0074] The shifting element and the photothermal element are in each case preferably related in terms of refractive index, the refractive index of the shifting element being preferably greater than the refractive index of air and / or the refractive index of the photothermal element.
[0075] Therefore, the refractive index of the shifting element is preferably different from the refractive index of the photothermal element or the surroundings, which leads to a change in the Fresnel coefficients and thus affects the optical properties of the heating device, i.e. the absorption and transmission behavior.
[0076] The shift element corresponds particularly preferably to the dielectric element mentioned above. That is to say, the shift element and the dielectric element can be provided by a single element. However, it is equally conceivable that the shift element and the dielectric element are separate elements. For example, in the latter case, a possible heating device can include, in this order, when viewed along the extension direction, a dielectric element such as a titanium dioxide layer or a layer made of a high refractive index dielectric, a shift element such as a semiconductor layer, for example made of Si, Ge or GaP, a photothermal element such as a gold layer containing a percolation structure at the percolation threshold, another shift element such as a semiconductor layer, and a dielectric element such as a titanium dioxide layer. In this case, it can be said that the two dielectric elements provide the upper and lower surfaces of the heating device.
[0077] The heating device preferably further includes at least one anti-reflective element constructed and arranged to reflect electromagnetic radiation towards the photothermal element.
[0078] The antireflection element preferably comprises two or more layers arranged above or stacked on top of one another in the extension direction, and these layers preferably have a refractive index that increases gradually in the extension direction.
[0079] Additionally, the antireflective element is preferably optically transparent and / or dielectric.
[0080] The antireflection element is preferably arranged in front of and / or behind the photothermal element in the extension direction. For this purpose, it is particularly preferred that the antireflection element provides the upper and / or lower surface of the heating device. Thus, in case the heating device comprises one or more dielectric or shifting elements as mentioned above, the antireflection element is preferably arranged closer to the outside of the heating device than the dielectric or shifting elements, respectively.
[0081] The heating device preferably further comprises at least one carrier element. The photothermal element is preferably arranged on the aforementioned carrier element or at least partially embedded in the aforementioned carrier element. If the heating device comprises one or more of the above-mentioned additional components, such as a dielectric element, a shifting element, an anti-reflection element, it is preferred that these one or more additional components are also arranged on the carrier element or at least partially embedded in the carrier element.
[0082] The carrier element is preferably bendable and / or flexible and / or deformable and / or foldable.
[0083] Furthermore, the carrier element may be optically transparent. Additionally or alternatively, the carrier element may comprise or consist of a solid, preferably an amorphous solid such as glass, and / or one or more plastics and / or one or more polymers. For example, the carrier element may comprise or consist of an optically transparent and / or elastic plastic or polymer.
[0084] Furthermore, preferably the carrier element is a layer which is preferably further adapted to be suspended, i.e. the carrier element is preferably a membrane.
[0085] The carrier element may serve the purpose of attaching or adhering the heating device to an end user device, such as a pair of glasses, on which condensation or ice formation is to be prevented.
[0086] However, it should be noted that the application or attachment of the heating device to the end user device does not necessarily require a carrier element. Instead, a direct application of the heating device, such as directly coating the optical thermal element on the eyeglasses, is equally conceivable. The provision of a carrier element provides the possibility of retroactively attaching the heating device to existing end user devices such as eyeglasses.
[0087] In another aspect, a method of manufacturing a heating device for preventing or removing deposits, in particular for condensation removal such as defogging, condensation prevention such as fog prevention, ice removal, or ice prevention, is provided. The heating device extends along an extension direction. The method includes providing at least one photothermal element configured to exhibit a photothermal effect when electromagnetic radiation is incident on the photothermal element. The photothermal element includes or consists of a photothermal material including a percolation structure. The percolation structure is at or substantially at its percolation threshold.
[0088] The heating device preferably corresponds to the heating device described above, so any explanation given with respect to the heating device preferably applies equally to the method for manufacturing the heating device and vice versa.
[0089] The photothermal element is preferably produced by deposition, preferably by thin film deposition and / or vapor deposition. In practice, the photothermal element is particularly preferably produced by chemical vapor deposition and / or physical vapor deposition, such as sputter vapor deposition, thermal evaporation, molecular beam epitaxy, atomic layer deposition or pulsed laser deposition. Alternatively, the photothermal element is produced by chemical growth.
[0090] Additionally or alternatively, the photothermal elements are preferably produced by island growth, in which individual islands are first formed by deposition and / or chemical growth, and said individual islands grow progressively during further steps of deposition or growth until a percolation structure is produced that is at or substantially at the percolation threshold.
[0091] For this purpose, it is particularly preferred that the photothermal element is produced according to the so-called Volmer-Weber growth method, which is well known in the art, in other words, the photothermal element is preferably produced by a stochastic nucleation and growth method.
[0092] The photothermal elements are preferably produced by deposition at a deposition rate in the range of 0.05 nm / sec to 1 nm / sec and / or during a deposition time in the range of 1 sec to 150 sec.
[0093] The photothermal element is produced by depositing at least one material, particularly preferably at least one conductive material or at least one semiconductor. A preferred conductive material is a conductive metal compound. As mentioned above, the metal compound may be an elemental metal or a metal alloy.
[0094] In a preferred example, in a first step, the dielectric element is formed using sputter deposition (with a Von Ardenne CS 320C). For example, a titanium dioxide (TiO2) layer of about 3 nm can be produced using the following parameters: RF field of 600 W, pressure of 6 μbar, deposition time of 71 seconds. The photothermal element can then be produced by thermal evaporation (Evatec BAK501 LL) of, for example, gold (Au) at a deposition rate of 0.05 nm / s until an estimated optimal layer thickness of 4.75 nm is reached. Finally, the Au layer forming the percolation can be covered by another dielectric element, such as another layer of TiO2 deposited under the same conditions as mentioned above.
[0095] For this purpose, it is particularly preferred that the photothermal element is produced by depositing a conductive material directly on a substrate such as the dielectric element, shift element, carrier element, or end-user device mentioned above. Thus, countering surface haze to maintain surface transparency is important for a wide variety of applications including eyewear, windows, or displays. Energy-neutral and passive approaches rely primarily on engineering the wettability of surfaces to achieve superhydrophilic or superhydrophobic coatings, but suffer from non-uniformity, contaminant deposition, and lack of robustness that significantly degrade the performance of these approaches. Herein, a sunlight-activated transparent photothermal heating device is used to completely suppress haze, based on nucleation thermodynamics. In particular, the present invention provides a rationally engineered photothermal heating device that can be only a few nm thick and has strong broadband absorption in the near-infrared region while maintaining high transparency in the visible region, making an important step forward toward implementable transparent photothermal surfaces to address haze-like deposit removal. Unlike the prior art, the heating device according to the invention strongly absorbs wavelengths invisible to the human eye while maintaining transparency in the visible range. The selective absorption in the near infrared spectrum can be achieved by a single, easily fabricated metal layer with a thickness in the nanometer range, at or substantially at the percolation threshold [37-40], optionally embedded in a dielectric host that can match the transparency peak of the photothermal heating device to the peak wavelength of solar radiation (occurring in the visible range). Due to its facile design concept and its optical selectivity, the heating device can be ultra-thin (about 10 nm) and is easily integrated over large areas above existing structures and below additional standard coatings that are usually deposited on transparent materials. This allows the heating device to be protected and long-lasting from outdoor influences such as chemicals, scratches or oxidation.Its thinness allows it to be fabricated even on compliant substrates with robust behavior against potential damage from repeated bending without loss of performance. Near infrared solar absorption and dissipation is utilized to prevent fogging (anti-fogging) and to rapidly recover from fogging (defogging) even under non-ideal real-world outdoor conditions. The heating device can be easily fabricated over large areas by standard methods (sputtering and thermal evaporation) with minimal material requirements supporting the feasibility of the heating device for direct use in applications.
[0096] Preferred embodiments of the present invention will now be described with reference to the drawings, which are for the purpose of illustrating the preferred embodiments of the present invention and are not intended to limit the invention. [Brief description of the drawings]
[0097] [Figure 1A] 1 is a schematic cross-sectional view of a heating device according to the present invention; [Figure 1B] 1 is a schematic cross-sectional view of a heating device according to the present invention; [Figure 1C] 1 is a schematic cross-sectional view of a heating device according to the present invention; [Figure 1D] 1 is a schematic cross-sectional view of a heating device according to the present invention; [Diagram 2] 1 is a scanning electron micrograph of a 15 nm thick gold layer. [Figure 3A] 1 is a graph showing the absorptivity of gold layers of different thicknesses. [Figure 3B] 1 is a graph showing the reflectivity of gold layers of different thicknesses. [Figure 3C] 1 is a graph showing the transmittance of gold layers of different thicknesses. [Figure 4A] FIG. 2 is a schematic diagram of a heating device. [Figure 4B] 1 is a graph showing the maximum average near infrared absorptivity of a heating device. [Figure 4C] 1 is a graph showing the transmittance and absorptance of a heating device. [Figure 5A]FIG. 1 is a schematic diagram of an experimental setup for simulating solar illumination of a heating device. [Figure 5B] 5B is a graph showing the photothermal performance of a heating device under solar illumination using the experimental setup according to FIG. 5A. [Figure 5C] 5B is a graph showing the photothermal performance of a heating device under solar illumination using the experimental setup according to FIG. 5A. [Figure 6A] 6A and 6B are graphs illustrating the anti-fogging performance of a heating device; FIG. 6A shows a plot of the temperature and overpressure of a heating device over time; [Figure 6B] 6A and 6B are graphs illustrating the anti-fogging performance of a heating device; FIG. 6B shows an image sequence recorded over time for a control sample and a heating device according to the present invention; [Figure 6C] 6A and 6B are graphs showing the anti-fogging performance of the heating device; FIG. 6C shows the fogging percentage for a control sample and a heating device according to the present invention; [Figure 7A] 7A and 7B are graphs and images showing the defogging performance and real-world feasibility of a heating device. FIG. 7A shows a qualitative image sequence of a control sample and a heating device according to the present invention under 1 sun illumination. [Figure 7B] 7A and 7B are graphs and images illustrating the fog elimination performance and real-world feasibility of a heating device. FIG. 7B plots the fog percentage over time for a control sample and a heating device according to the present invention. [Figure 7C] 7A and 7B are graphs and images showing the anti-fog performance and real-world feasibility of the heating device; FIG. 7C shows images from outdoor testing of glasses without a heating device according to the present invention and glasses including a heating device according to the present invention in different locations and under different levels of solar irradiance. [Figure 7D] 7A-7D are graphs and images illustrating the defogging performance and real-world feasibility of a heating device. FIG. 7D shows a bend test of a heating device according to the present invention placed on a transparency of an overhead projector. [Figure 7E]7A and 7B are graphs and images showing the defogging performance and real-world feasibility of the heating device; FIG. 7E shows an image from an outdoor test of a heating device according to the present invention placed on the transparent sheet of an overhead projector according to FIG. 7D. [Figure 8] 1 is a graph showing nucleation rate as a function of temperature for sample temperature. [Figure 9] 4 is a graph showing the optical characteristics of a heating device according to the present invention including photothermal elements of different thicknesses. [Figure 10] 1 is a scanning electron microscope image of photothermal elements of different thicknesses. [Figure 11] 1 is a graph showing four-probe measurements of photothermal elements of different thicknesses. [Figure 12] 4 is a graph showing the angular dependence of transmittance of a heating device according to the present invention. [Figure 13] 1 is a graph showing advancing and receding contact angles for bare fused silica (SiO2), a control sample (TiO2 coated fused silica), and a heating device according to the present invention. [Figure 14A] 14A-14C are graphs and images of defogging experiments; FIG. 14A shows exemplary results of defogging experiments for a control sample and a heating device according to the present invention; [Figure 14B] Graphs and images of the defogging experiment. FIG. 14B shows an image sequence looking down on the defogging area of the two exemplary experimental runs shown in FIG. 14A. [Figure 14C] Graphs and images of the defogging experiment. FIG. 14C is a graph showing the defogging time required for the control and the heating device to be less than 5% covered with fog. [Figure 15A] 1 is an image of an outdoor test with a pair of vision glasses with glasses including a heating device according to the invention and glasses without a heating device according to the invention. [Figure 15B] 1 is an image of an outdoor test with a pair of vision glasses with glasses including a heating device according to the invention and glasses without a heating device according to the invention. [Figure 15C]1 is an image of an outdoor test with a pair of vision glasses with glasses including a heating device according to the invention and glasses without a heating device according to the invention. [Figure 16A] FIG. 1 shows the experimental setup for outdoor experiments of photothermal effects. [Figure 16B] 4 is a graph showing the temperature progression of a control sample and a lens including a heating device according to the present invention. [Figure 17A] FIG. 17A shows the effect of a heating device according to the present invention disposed on a flexible substrate. FIG. 17A is a graph showing the transmittance and absorptance of a substrate (overhead projector transparency) containing a heating device, and the transmittance for a curved sample, before (solid line) and after (dashed line) 300 bending cycles. [Figure 17B] FIG. 17B shows an image of the curved sample (40°) shown in FIG. 17A, illustrating the effect of a heating device according to the present invention disposed on a flexible substrate. [Figure 17C] FIG. 17C shows a photograph of a fully bent sample during a bending cycle, illustrating the effect of a heating device according to the present invention disposed on a flexible substrate. [Figure 17D] FIG. 17D shows a photograph of a compliant substrate / foil that can be attached to any existing glass to prevent fog formation or accelerate fog removal. [Figure 18a] FIG. 18a shows the effect of the angular dispersion relationship of a heating device according to the present invention; FIG. 18a is a schematic diagram of a heating device according to the present invention, which includes a gold layer at the percolation threshold embedded between two titanium dioxide layers on a substrate in the form of silicon dioxide. [Figure 18b] FIG. 18b shows the effect of the angular dispersion relationship of a heating device according to the present invention; FIG. 18b shows a scanning transmission electron microscope image (left) and energy dispersive X-ray spectroscopy mapping (right) of the heating device. [Figure 18c]FIG. 18c is a graph showing the effect of the angular dispersion relationship of the heating device according to the present invention, and shows the angular dispersion relationship of the absorptance versus radiation incidence angle θ up to 30° relative to the normal to the heating device. [Figure 19A] 1 is a graph showing broadband absorptance in the near infrared spectrum of a heating device according to the present invention. [Figure 19B] 1 is a graph showing broadband absorptance in the near infrared spectrum of a heating device according to the present invention. [Figure 20a] Bright-field SEM image of a heating device containing a photothermal structure at the percolation threshold. The photothermal material is Au (black) and is uniformly surrounded by a TiO2 layer (dark grey). A SiO2 substrate is on the bottom, while the top is covered with carbon to facilitate imaging (both light grey). [Figure 20b] High-resolution transmission electron microscopy. The actual thickness of the Au layer (for dAu = 4.75 nm) is estimated to be about 6-7 nm, while the TiO2 is about 2-3 nm (for dTiO2 = 3 nm). Scale bar: 10 nm. [Figure 21] Figure 1 shows a graph of the angular dependence of the optical properties. Incident radiation measurements are performed at an angle θ with respect to the normal to the heating device. The measured transmittance and reflectance are displayed in the top and middle panels, respectively. From these the absorptance is estimated and shown in the bottom panel. [Figure 22] FIG. 2 shows a comparison of the heating device according to the invention with a photothermal anti-fog coating according to the prior art as a function of the visible transparency τ VIS and the solar absorption α solar per material thickness d (in nm). [Diagram 23] Figure 1 shows photothermal results at low levels of solar irradiance. Box plots (n=5) of steady-state temperature rise of the heating device according to the invention and the control sample under different levels of solar irradiance I0 including 0.2 and 0.4 suns. The box plot includes a center line, upper and lower quartiles, and whiskers (1.5 times the interquartile range). [Figure 24a]FIG. 13 illustrates an outdoor test of a heating device according to the present invention using a pair of prescription eyeglasses. [Figure 24b] FIG. 13 illustrates an outdoor test of a heating device according to the present invention using a pair of prescription eyeglasses. [Figure 25a] FIG. 2 shows a laboratory test of a heating device according to the invention behind a triple-glazed window. [Figure 25b] FIG. 2 shows a laboratory test of a heating device according to the invention behind a triple-glazed window. [Figure 26A] FIG. 1 shows a heating device disposed on different polymer substrates, including flexible substrates. Panel A) shows the absorption α of bare polymer (grey) and coated substrate. [Figure 26B] FIG. 1 shows heating devices disposed on different polymer substrates (including flexible substrates). Panel B) shows an SEM micrograph of the as-fabricated heating device (without a TiO2 top layer to facilitate imaging). Scale bar B): 100 nm. [Figure 27A] Figure 1 shows heat and abrasion resistance tests: A) Evolution of Ts over 50 cycles under exposure of about 1 sun. [Figure 27B] Figure 13. Heat and abrasion resistance tests: B) Absorbency α before (grey) and after (dark grey) 50 temperature cycles. [Figure 27C] Figure 13. Heat tolerance test. C) Increase in Ts above Tamb in the first 5 hours of a 63 hour sun exposure test. [Figure 27D] Figure 13. Heat resistance test. D) Absorbency α before (grey) and after (dark grey) a 63 hour sun exposure experiment. [Figure 27E] Figure 14. Abrasion resistance test. E) Permeability τ of the heated device before and after the peel test. [Figure 27F] Figure 14. Abrasion resistance test. F) Permeability τ of the heating device before and after the wipe test. [Figure 27G] Figure 14. Wear resistance test. G) Permeability τ of the heating device before and after the wear resistance test by ablation. [Fig. 27H] Figure 14: Abrasion resistance test. H) Permeability τ of the heating device before and after the abrasion resistance test with falling sand. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0098] Various embodiments of the heating device 1 according to the invention will now be described with reference to the drawings.
[0099] As can be seen from Figures 1A-1D, the heating device 1 extends along an extension direction E and comprises at least one photothermal element 2 configured to exhibit a photothermal effect when electromagnetic radiation is incident on it. The photothermal element 2 consists of a photothermal material including a percolation structure, the percolation structure being at or substantially at its percolation threshold.
[0100] In the illustrated embodiments, the heating device 1 is in each case arranged on a carrier element 7. Furthermore, in all illustrated embodiments, the heating device 1 is provided as a laminate structure, i.e. the photothermal element 2 and the further components of the photothermal element 2 which will be described with reference to Figures 1B to 1D are layers extending along a transverse direction T which runs perpendicular to the extension direction E.
[0101] 1A, the heating device 1 can include at least one electrical element 3 configured to induce an electric current in the photothermal element, thereby generating heat by the photothermal element. In the illustrated example, the electrical element 3 is an electrode disposed on the photothermal element 2.
[0102] As mentioned above, further possible components of the heating device 1 are shown in Figures 1B-1D. Namely, the heating device 1 can further comprise at least one dielectric element 4. Here, two dielectric elements 4 are provided, one of which is arranged in front of the light-heat element 2 with respect to the extension direction E and the other one is arranged after the light-heat element 2 with respect to the extension direction E. For this purpose, the dielectric element 4 and the light-heat element 2 are in full surface contact with each other.
[0103] The heating device 1 additionally comprises at least one shift element 5, which is configured to shift the absorption and / or transmission capacity of the heating device 1 with respect to the incident electromagnetic radiation towards shorter or longer wavelengths of the incident electromagnetic radiation. In Fig. 1B-1D, the dielectric element 4 and the shift element 5 are provided by the same element, i.e. the dielectric element 4 corresponds to the shift element 5 and vice versa. However, as can be seen from Fig. 1D, the shift element 5 can also be provided as an additional component. Furthermore, the dielectric element 4 may not correspond to the shift element 5 in any case, but may, for example, only be used for the purpose of electrically insulating the photothermal element 2.
[0104] The heating device 1 may additionally include at least one anti-reflective element 6 constructed and arranged to reflect electromagnetic radiation towards the photothermal element 2. Such embodiments are shown in Figures 1C and 1D, in which in each case the anti-reflective element 6 is arranged in front of further components of the heating device 1. In these cases, the anti-reflective element 6 provides a top surface 8 of the heating device 1.
[0105] Although not shown in Figures 1A-1D, the heating device 1 can be attached or coated on some surface to prevent or eliminate deposits from said surface. The heating device 1 can therefore be considered as a coating on said surface. Therefore, the expression "coating" as used hereinafter in this specification should be understood as the heating device according to the present invention.
[0106] Furthermore, the expression "metamaterial" should be understood as a photothermal element that includes or consists of a photothermal material that includes a percolation structure, and the percolation structure is at or substantially at its percolation threshold.
[0107] Heating device design 3A-4C show the design and optical characteristics of the heating device.
[0108] Unlike the gold layer shown as a scanning electron micrograph in FIG. 2, which has a thickness of 15 nm, is flat, continuous and is formed of polycrystalline domains, the heating device of FIGS. 3A-4C includes photothermal elements in the form of gold layers containing percolation structures, which are associated with specific absorptivity, reflectivity and transmittance properties depending on the thickness of the gold layers. To this end, FIG. 3A shows the absorptivity of gold (Au) layers of different thicknesses, i.e. different thickness parameters, embedded between dielectric layers in the form of upper and lower 3 nm TiO2 layers. The spectrally resolved absorptivity in the visible and near infrared range shows a maximum in this region when the layer thickness parameter is 4.75 nm. FIG. 3B shows the reflectivity of gold (Au) layers of different thicknesses embedded between upper and lower 3 nm TiO2 layers. The spectrally resolved reflectivity increases as the film grows, forming a continuous and flat mirror. Figure 3C shows the transmittance of a gold (Au) layer of different thicknesses, i.e., different thickness parameters, embedded between two upper and lower TiO2 layers with thickness parameters of 3 nm each. The spectrally resolved transmittance shows good transparency in the visible range. The absorptance at the interband transitions of gold, red-shifted by the TiO2 matrix, is lower than the absorptance in the near-infrared range.
[0109] Furthermore, Figure 4A shows that NIR is absorbed by the heating device and dissipated into heat (photothermal effect), while the heating device is mostly transparent in the visible range. The resulting increase in surface temperature prevents fogging. Figure 4B shows the maximum average near-infrared absorptance
number
[0110] Therefore, in order to efficiently collect solar energy to combat fogging and at the same time maintain transparency, the design of the coating, i.e. the heating device according to the present invention, targeted high broadband absorbency in the near infrared (NIR, λ=720-2000 nm) solar radiation spectrum and high broadband transparency in the visible spectrum (VIS, λ=400-720 nm), as shown in FIG. 4A. In fact, the NIR solar spectrum accounts for about 50% of the incident solar irradiance I0, thus offering great potential for collecting solar energy that is invisible to the human eye. Once absorbed, this solar energy dissipates itself as heat, increasing the sample temperature T s The ambient temperature T ambabove T, thereby reducing the risk of clouding and preserving the transparency of the sample in the VIS spectrum. Considering the very sensitive dependence of the nucleation rate of condensates on temperature [41-44], this thermodynamic approach is powerful and, unlike many existing methods, does not rely on chemistry [45-47]. In order to exponentially decrease the nucleation rate of droplets and thereby reduce the probability of a nucleation event by several orders of magnitude, T s It is sufficient to slightly increase the temperature (see FIG. 8). The maximum temperature increase is achieved when the photothermal coating, i.e. the heating device according to the invention, has a strong broadband absorption in the NIR spectrum. Previous studies have shown that good NIR absorption can be achieved by using metal particles. These metal particles have a large cross-sectional area and therefore a strong light absorption at the plasmon resonance frequency in the VIS spectrum, and by mixing metal nanoparticles of different sizes and shapes, this narrowband absorption can be extended over a wider spectrum into the NIR [Non-Patent Documents 10, 17, 23, 48]. It has also been shown that structured particles can be used to selectively absorb the NIR spectrum. However, these particles are narrow-band absorbing and require complex and delicate fabrication [Non-Patent Documents 49-51]. In contrast, the idea of a single thin metal layer at or substantially at the percolation threshold is proposed. In this state, unconnected clusters of individual nano-islands coalesce into larger connected patterns. This leads to non-localized surface modes, which result in strong and broadband absorption of the incident radiation in the NIR [52,53], which is then converted into heat. To realize this concept, a thin layer of gold (Au) is deposited using a commercial technique (thermal evaporation) to a layer thickness d Au was adjusted to be at or substantially at the percolation threshold (see Figures 9-11).
[0111] Figure 4B shows the average NIR absorptance
number
[54] . The spectral response of the as-fabricated heaters was measured and their optical properties were characterized. Figure 4C shows the high transmittance (τ) in VIS that matches well with the peak of solar irradiance I0. VIS = 67.1%). Furthermore, due to the random nature of the percolation pattern, the transmittance becomes independent of the angle of incidence of the incident light (Fig. 12). At the same time, the heating device exhibits strong broadband absorption in the NIR (α NIR= 36.9%). Clearly, at the percolation threshold, the plasmon resonance (which normally causes a strong localized absorption at the resonance frequency) is replaced by a broadband absorption below the resonance frequency, i.e. in the NIR spectrum. Similarly, the heating device remains transparent to shorter wavelengths in the VIS spectrum, since it remains optically thin. The strong transmission around λ = 550 nm comes from the interband transitions of gold [55,56]. Here, the structural absorption in the NIR induced by percolation is stronger than the interband transitions of the thin film in the visible range. As a result, the heating device collects about 30% of the incoming solar energy (280-2000 nm) at only about 10 nm, while remaining transparent.
[0112] Next, the photothermal performance of the heating device was evaluated. This will be described with reference to FIG. 5, which shows the experimental setup and photothermal performance. In particular, FIG. 5A shows a schematic diagram of the experimental setup. The samples (control and heating device coating, i.e., the heating device deposited on a substrate, which here is SiO2) were subjected to 600-1000 Wm -2 The specimen is illuminated with an irradiance of 100 nm (corresponding to 0.6–1 sun). A color camera and its objective lens image the formation of haze on the coated underside of the specimen. Warm steam diffuses from a copper pipe at a controlled temperature onto the surface of the specimen.
[0113] In particular, the surface temperature T of a fused silica (SiO2) substrate coated with a heating device under simulated solar illumination (see the experimental setup shown in Figure 5A) s was measured. As a control sample, a thin layer of TiO2 of about 3 nm was deposited on a SiO2 substrate to obtain the same wetting behavior as the heating device (Fig. 13). The sample is placed on the sample holder so that the coated side of the substrate faces downwards. The irradiance I0 is controlled by the shutter of the solar simulator. I0 of 1 sun (1000 Wm -2) results in the highest measured photothermal response. However, in outdoor conditions, I0 is often less than 1 sun. Thus, 600 and 800 Wm2, which correspond to 0.6 and 0.8 sun, respectively, -2 The temperature response to weaker irradiance was also recorded. Under 1 sun illumination, a heating device coated on a SiO2 substrate was heated to ambient temperature (T s -T amb , see FIG. 5B). s The ambient temperature (T amb ≈23°C, RH≈55%), whereas the heater on the SiO2 substrate heats up significantly even under weaker irradiance (5.4°C at 0.6 sun and 6.4°C at 0.8 sun, respectively). Note that this increase is more than enough to reduce the condensate nucleation rate by several orders of magnitude (see Figure 8). This experimental observation is in close agreement with a transient heat transfer model that validates the temperature measurements. In this model, the convection heat transfer coefficient h conv Only the values in the reasonable
[57] range (8.5–10.5 Wm -2 K -1 ) (see Supplementary Note 4). Figure 5C summarizes the steady-state temperature rise (t = 230 s) of the heating device on a SiO2 substrate and the control sample, demonstrating the remarkable photothermal response of the former heating device. Regardless of the illumination, the heating device on a SiO2 substrate significantly outperforms the control by at least 5 °C.
[0114] The performance of the heating device on a SiO2 substrate was then tested in terms of resistance to fogging of the surface (fogging prevention) (see Fig. 5B and Fig. 5C). That is, Fig. 5B shows the average temperature rise (dashed line) and standard deviation (shaded area) of the surface under solar illumination from 0.6 to 1 sun. The solid line represents the temperature transient heat transfer model, which matches well with the experimental results. Fig. 5C shows the box plot of the temperature rise at steady state (t = 230 s) of the heating device on a SiO2 substrate and the control sample under different solar irradiances I0 (from 0.6 to 1 sun). For this, in the experimental setup, a heated copper tube is installed, which is connected to a bubbler filled with water and a shutter at the tube outlet. As shown in Fig. 5A, the steam impinges on the sample surface from the same side as the sample is illuminated. The steam temperature T v is controlled via a copper tube (surrounded by a heating cable) and measured very close to the sample. T v and T s ≒T amb Since the vapor pressure of the supplied moist air p is known, v In addition to the saturated vapor pressure of air very close to the sample, p sat (Arden-Bach equation
[58] ) can be calculated.
[0115] FIG. 6 shows the anti-fog performance. In fact, FIG. 6A shows the change in the (heated device coated) sample temperature T s and overpressure p v -p sat First, the sample is illuminated by a solar simulator (here, 1 sun). After 2 minutes of sun exposure, the steam shutter is opened for 5 seconds to expose the sample to steam. Then, the overpressure (p v -p sat The shutter was closed for 20 seconds to allow T to return to its initial condition. This sequence was repeated 5-7 times for each experiment. The sequence was then averaged to provide the mean and standard deviation. As shown in Figure 6A, T airAnd, by extension, p v -p sat and reach peak values and then equilibrate back to their initial values within about 15 seconds. At the same time, the formation of condensate on the surface of the sample was recorded. Dark-field imaging of the haze allowed to identify the areas of the sample where droplets formed. Small droplets present on the surface backscatter part of the incident light and provide good brightness to the camera. The recorded image was then binarized with respect to its brightness and the area covered by the haze, i.e. the haze fraction of the surface, f = A fog / A sample is quantified. Here, A fog is the area covered by clouds, and A sample is the total area of the sample.
[0116] FIG. 6B shows a sequence of images recorded over time of a control under 1 sun and under substantially the same overpressure and a heating device on a SiO2 substrate. The considered area A of the sample used to determine the haze fraction f sample is shown. Before the shutter is opened (t=5 s), there is no fogging (f=0) on both the control and the heating device on the SiO2 substrate, i.e., at t=5 s, there is no fogging (f=0) on both samples. When the steam shutter is opened, the samples start to fogging and reach their respective peak fogging fractions. To this end, the fogging fraction f is gradually increased and reaches its peak at t=10 s, i.e., at the same pressure difference p v -p sat At (1.56 and 1.62 kPa, respectively), f = 1 is reached for the control sample and an order of magnitude lower (f = 0.12) for the heated device on the SiO2 substrate. After 20 seconds (t = 25 seconds), the heated device on the SiO2 substrate is already completely free of fogging, while the control sample still needs additional time to fully recover its initial state before the next cycle. To quantify this impressive anti-fogging performance, different levels of p v -p satFurther experiments were carried out under different solar illuminations (0.6, 0.8, and 1 sun). For each experimental run, the overpressure p v -p sat and the measured haze fraction f, the average value and the corresponding standard deviation are provided.
[0117] FIG. 6C shows the results of the experiment under different solar illumination and different levels of overpressure p v -p sat Figure 6C shows the haze fraction f of the heater coating on SiO2 substrate under different illumination levels and the control sample. The inset table shows that the fog prevention of the heater coating on SiO2 substrate is improved by more than 4 times over the control at all illumination levels. Scale bar B): 5 mm. The experimental results follow a linear trend as shown in Figure 6C. The much stronger fog resistance of the heater on SiO2 substrate compared to the control sample is evident in the significantly smaller slope under partial fog and the overpressure value where fog starts to form (f>0). By linear fitting, it is possible to identify the corresponding overpressure where the sample is completely free of fog (f=0) and completely fogged (f=1). These p v -p sat Using the values of p, it was estimated that the fogging resistance of the heating device on the SiO2 substrate was improved over the control sample. As shown in the inset table of Figure 6C, the control sample had p v -p sat At p = 0.67, 0.69, and 0.78 (0.6, 0.8, and 1 sun), the heating device is completely covered by the cloud (f = 1). In stark contrast, the heating device on the SiO2 substrate is covered by the cloud at p v -p sat = 2.76, 2.91, and 3.82 (0.6, 0.8, and 1 sun), it only becomes completely fogged (f = 1). This suggests that the heating device on the SiO2 substrate impressively withstands 4.12 to 4.9 times higher overpressure compared to the control sample, which suggests a more than four-fold improvement in anti-fog performance.
[0118] After the defogging experiment, the defogging performance of the heating device on the SiO2 substrate was evaluated, i.e., the recovery of visibility after the surface was completely defogging. For this purpose, the control sample and the heating device on the SiO2 substrate were tested under ambient conditions (T amb ≈23 °C, RH ≈55%) over 2 min until condensation formed, and the sample was then immediately placed on the experimental setup (see Fig. 5A) and illuminated by sunlight while recording the evolution of the haze on the surface.
[0119] FIG. 7 shows the defogging performance and feasibility in the real world. In fact, FIG. 7A shows the defogging performance under 1 sun illumination (T amb 1 shows a qualitative image sequence of a control sample and a heater-coated sample at ≈23 °C, RH ≈55%) and over the period t = 0 to 150 s. The heater coating on the SiO2 substrate is completely dehazed in less than 150 s and to a large extent (f ≈ 0.25) in less than 100 s, while the control sample remains almost hazy over this same period. That is, the control is still covered with haze at t = 150 s, whereas the heater coating on the SiO2 substrate has fully regained its transparency. The small size of the condensed droplets causes a large scattering and therefore a very white image of the sample in dark-field imaging, which is clearly discernible in the image of the control at t = 0 s. In the case of the heater-coated sample, the dehazing front progresses much more quickly compared to the control sample (see Fig. 14). Under different levels of illumination (T amb Experiments at ≈23 °C and RH ≈55%) will provide a more thorough quantification of the defogging dynamics.
[0120] From this data, the evolution of the haze fraction f over time was extracted, as shown in FIG. 7B. That is, FIG. 7B shows the evolution of the haze fraction f over time for the control sample and the heater coating on a SiO2 substrate. The latter heater coating begins to clear haze much earlier and more rapidly (steeper) than the control sample. This coating has a t d Reduce the defogging time t by a factor of 2 to 3. d was defined and determined as the time required for f<0.05, i.e., for the sample to be less than 5% covered with fog. The control sample remained completely fogged for a much longer period of time (f≈1), and its fog elimination rate (FIG. 7B) was much slower. Specifically, under the given experimental conditions and 1 sun illumination, the average fog elimination time for the heated coated sample was
number
number
number
number
number
[0121] Leveraging this knowledge of improved anti-fog / defog performance, the real-world feasibility of the heating device was tested under outdoor conditions. For this, one lens of a pair of prescription glasses was coated with the heating device and placed outdoors on a sunny winter day. After 5 minutes of sun exposure, the glasses were donned and exhaled while wearing a tight-fitting face mask (FFP2), mimicking real-world conditions experienced on a daily basis these days. This warm breath acts like a supersaturated flow of vapor, impinging on both the uncoated lens (at ambient temperature) and the lens coated with the heating device (which has a temperature noticeably elevated above ambient due to photothermal effects).
[0122] FIG. 7C shows the results at two different locations. In particular, FIG. 7C shows the results at different locations and at different levels of solar irradiance (I0 above=212 Wm -2 , I0=339Wm -2 15 shows images of outdoor testing under different outdoor temperature measurements. The left lens of the glasses is coated with a heating device and maintains its visibility under moist human breath leaking upwards from the mask, whereas the uncoated lens fogs up. Clearly, even under such non-ideal conditions, a strong improvement in anti-fog / defog performance is evident. Further outdoor experiments of coated and uncoated lenses at different locations and different outdoor temperature measurements can be seen in FIG. 15 and FIG. 16.
[0123] Finally, the applicability and effectiveness of the heating device in preventing fogging of flexible materials was tested, as shown in Figure 7D, which shows a bending test of a heating device coated overhead projector transparency.
[0124] For this purpose, a polyester sheet (transparency of an overhead projector) is coated with the heating device and the optical properties of the coated sheet are measured. Then, as shown in FIG. 7D, the sheet is bent 300 times, after which the optical properties are measured again to test the robustness of the sheet against repeated severe deformations. Since the coating is only about 10 nm thick, the relatively large radius of curvature due to bending deformation does not cause mechanical damage to the heating device coating or deteriorate the optical properties (the random arrangement of metamaterials, i.e. photothermal elements including or consisting of photothermal materials that are at the percolation threshold, which is of the order of hundreds of nm, or that include percolation structures that are substantially at the percolation threshold, is much smaller than the bending radius of curvature). Thus, the heating device, thanks to its thinness, is resistant to severe deformations and can be easily applied on flexible, foldable and portable substrates. Additionally, the heating device can be placed on any portable, flexible / foldable material and can be retroactively attached onto existing surfaces such as windows, shields, or glasses.
[0125] The feasibility of this approach was further proven by taping a polyester sheet onto a heater-coated fused silica wafer and testing the anti-fog / defog performance when exhaling multiple times on the wafer and coating in a pile. Clearly, as shown in FIG. 7E (also FIG. 17), the transparency with the coating defogs much faster, proving its feasibility under harsh outdoor conditions. That is, FIG. 7E shows an outdoor test proving that an overhead projector transparency with heater coating can be attached to any existing glass to prevent fog formation or accelerate fog defog. Scale bars A): 5 mm, C) and D): 10 mm, E): 20 mm.
[0126] Thus, an ultrathin heating device with high transparency in the VIS spectrum and strong absorptance in the NIR is presented. Spectral selectivity with broadened absorptance in the NIR is achieved by the structural percolation effect of a metallic Au nanofilm sandwiched between two dielectric TiO2 nanolayers resulting in a heating device with a total thickness of about 10 nm. Thanks to its ultrathin nature and its standard fabrication process, the heating device can be easily upscaled and deposited over large areas or integrated into existing multilayer coatings to add anti-fogging functionality. The percolation-induced light absorption of the metallic Au film leads to a photothermal response of up to 8.3°C temperature increase above ambient temperature under 1 sun illumination. This thermal response is exploited to exponentially decrease the nucleation rate of water vapor nucleation, resulting in an approximately 4-fold improvement in fog resistance (anti-fogging). Moreover, the visibility of fully fogged coated samples is restored up to 3 times faster (defog) compared to uncoated control samples. Importantly, the heating device has been shown to perform well even under relatively difficult conditions, such as 0.6 or 0.8 sun illumination. The actual performance of the heating device has been verified by applying it to prescription eyeglasses to demonstrate the heating device's impressive anti-fog effect under real outdoor conditions. Finally, the ultra-thin design of the heating device allows for easy application onto flexible, foldable, and portable substrates, and the heating device fully retains its optical and photothermal properties even under and after vigorous repeated bending.
[0127] method Sample preparation and optical characterization To fabricate the heating device and the control samples, a 500 μm thick JGS2 fused silica wafer was used as the substrate (UniversityWafer) diced into 22×22 mm squares. All specimens were ultrasonically cleaned in acetone and rinsed with isopropyl alcohol and deionized water for 2 min. Finally, the specimens were exposed to oxygen plasma for 5 min (Oxford Instrument, Plasmalab 80 Plus). Then, the coatings of the heating device and the control were produced by deposition:
[0128] Heating equipment: First, a titanium dioxide (TiO2) layer of about 3 nm was formed using sputter deposition (Von Ardenne CS 320 C) with the following parameters: RF field of 600 W, pressure of 6 μbar, deposition time of 71 s. Immediately afterwards, gold (Au) was thermally evaporated at a deposition rate of 0.05 nm / s until the estimated optimal layer thickness was reached, i.e. thickness parameters of 4.75 nm (Evatec BAK501 LL). Finally, the percolation-forming Au layer is covered by another layer of TiO2 deposited under the same conditions as mentioned above. In the parametric study to identify the percolation limit (see Supplementary Note 2), this last step of depositing TiO2 was not performed to allow four-probe measurements.
[0129] Control: For the control, a layer of TiO2 (about 3 nm) is deposited using the same parameters used to fabricate the heating device. The transmittance and reflectance were measured at normal incidence (0.25-2.0 μm) using a UV / VIS NIR spectrometer (Jasco, V770) equipped with an ILN-925 integrating sphere.
[0130] The average transmittance in the visible range is
number
number
[0131] Experimental setup To evaluate the anti-fogging and defogging performance, a dedicated experimental setup was developed (see Fig. 2A). The sample is placed upside down on a U-shaped sample holder (polymethylmethacrylate base, polystyrene foam on top, aperture width: 18 × 18 mm). A solar simulator (Newport, 66984-300XF-R1) equipped with an air mass filter (AM1.5Global) simulates sunlight. A shutter and diaphragm at the simulator aperture allow to set the exact start of the experiment and the illuminated area on the sample. The sunlight is deflected by a mirror towards the investigated sample. A CMOS color camera (FLIR BFS-U3-51S5C-C) with an objective lens (MVL7000-18-108 mm) images the sample. The solar irradiance is between 600 and 1000 Wm -2The temperature is adjusted from 0.25° C. and measured with a thermal power sensor (Thorlabs S425C and PM100 USB controller) at the same position and height as the sample is placed. For the fogging experiment, the bubbler inlet is connected to a nitrogen (N2) source (2.5 bar pressure, reduced using a Swagelok pressure valve) and filled with water. The bubbler outlet is connected to an insulated copper tube (outer diameter: 1 cm) whose temperature is precisely controlled by a heating cable (Horst™ 020101, 0.6 m, 75 W, and Horst™ 060271, HTMC1 / V controller) with a feedback signal from a resistance temperature detector (RTD, PT100). The bubbler is placed in a pan filled with water, which is heated by a hotplate (VWR, Advanced Series 444-0592). To ensure that the steam is always saturated, the water-filled pan is heated to a temperature higher than the required steam temperature in the copper tube. A glass slide at the outlet of the copper tube acts as a steam shutter. Five different temperatures are recorded simultaneously (all these temperatures are measured using PT1000 sensors): the temperature of the ambient air, the temperature of the sample, the temperature of the air / steam just below the sample (where condensation occurs) and the temperature of the steam just at the outlet of the copper tube). Additionally, the temperature in the water-filled pan was recorded using a PT100 sensor. All sensors are connected to a LucidControl RI8 USB logger. Before the experiment, all temperature sensors are calibrated (Fluke9142).
[0132] Using the above setup, two different types of experiments can be performed: Anti-fogging: Place the corresponding sample on the sample holder and start logging the temperature. After 10 seconds, the solar simulator shutter is opened. After 2 minutes of sun exposure, with the steam shutter still closed, open the N2 valve. The system is allowed to equilibrate for another 2 minutes before starting the experiment. The sample is exposed to the steam flux for 5 seconds before closing the shutter for 20 seconds, and this sequence is repeated 5-7 times while recording the surface by the CMOS camera.
[0133] Defogging: A Peltier module (Laird MS2-192-14-20-11-18) is placed on an optical table (heat sink) with thermal paste. A voltage of 2.8 V is then applied, resulting in a defogged Peltier module under ambient conditions (T amb ≈23 °C, RH ≈55%), resulting in a cold-side temperature of about 2 °C of the Peltier module. The Peltier is then cleared of ambient condensation and the sample is placed on a dry surface. After 2 minutes, the sample is lifted and placed on the sample holder, which is already exposed to solar illumination. A CMOS camera is used to record the time course of the haze on the surface.
[0134] Threshold To quantify the time evolution of the haze fraction f, we binarize all frames (captured by the CMOS camera) of the partially hazy control sample and the heated device coated sample. Using a dark field optical setup, condensed droplets in the hazy areas backscatter the incident light and appear bright, whereas the non-hazy transparent areas remain dark. The binarization threshold is set such that the non-hazy (reference) surface has f≈0 and the completely hazy white appearing areas have f≈1. The binarization level was manually initialized to a reasonable threshold and hole-like patterns were taken into account.
[0135] Linear fitting of anti-fog experiments A linear regression of the experimental data was performed to identify the overpressure at which the sample was completely free of haze (f=0) and the overpressure at which the sample was completely hazy (f=1). Since the haze fraction f ranges from 0 to 1, the linear fit excluded all data points with mean haze fraction f<0.05 and f>0.95.
[0136] Outdoor Testing The left lens of prescription grade eyewear (Rodenstock (Schweiz) AG) was coated with the heating device using the same parameters as described above. In the experiment, the glasses were first exposed to sunlight for about 5 minutes. Next, the operator donned a face mask (FFP2) and carefully adjusted the nose piece of the face mask so that the spacing between the left and right sides was substantially the same. Finally, the operator put on the glasses, took a deep breath, and exhaled while the fog formation on the glasses was recorded (Samsung Galaxy S20, Canon EOS 5D Mark4). The glasses were tested at multiple locations. Global horizontal irradiance (GHI) data was obtained from MeteoSwiss, and humidity and temperature data were obtained from MeteoSwiss or timeanddate.de.
[0137] Supplementary Note 1: Effect of sample temperature on nucleation thermodynamics Starting from classical nucleation theory, we calculate the change in the Gibbs free energy for a spherical nucleus during homogeneous nucleation as a function of its radius r as follows
[42] :
number
[58] . For p, we assume saturated vapor at a temperature equivalent to the human body / breath impinging on the sample, i.e., relative humidity RH=100% and T=36°C, which mimics the real-world conditions people regularly experience these days when wearing glasses and face masks. At the same time, p L is the sample temperature T s Finally, to account for the presence of insoluble flat surfaces that promote heterogeneous nucleation, equation (S1) can be modified as follows
[42] :
number
[44] , i.e., the cosine of the contact angle θ (=80°) of water on a flat surface. The critical radius r* required for a nucleus to grow into a larger droplet can be determined by setting ∂ΔG / ∂r=0, which gives us
[42] :
number
[0138] The corresponding critical Gibbs free energy at r = r* can be derived by substituting equation (S3) into (S2) and becomes
[42] :
number
[0139] Finally, the nucleation rate (J), i.e., the probability that a nucleation event will occur per unit area of surface, is given by
[42] :
number
[42] :
number
[0140] Figure 8 shows the sample temperature T s shows the nucleation rate J as a function of the sample temperature T s We show how J decreases significantly with a small increase in T in equation (S5). s The inverse exponential dependence on T results in a dramatic decrease in the nucleation rate. s When T increases from 20 to 22 °C, J decreases by five orders of magnitude. s A slight increase in results in an exponential decrease in the nucleation rate. This demonstrates that the heating device has a significant impact for anti-fogging / defogging applications due to its photothermal properties. The ambient conditions are set at RH: 100%, T=36°C, which represents saturated human breath.
[0141] Sidebar 2: Heating device characterization A parametric study was carried out by varying the thickness of the deposited gold layer (Au) to identify the thickness parameters at which the layer has the best overall absorptivity. For this, different thicknesses of Au (see Methods above for thickness parameters) are deposited on a layer of 3 nm TiO2. The Au layer is then covered by another 3 nm layer of TiO2 (see Methods). The transmittance (τ) and reflectance (R) of all samples are then measured (Jasco, V770 with an ILN-925 integrating sphere at normal incidence) immediately after deposition to identify the absorptivity (α=1-τ-R) over wavelengths λ=200-2000 nm.
[0142] FIG. 9 shows the optical properties of Au layers of different thicknesses embedded in 3 nm TiO2 top and bottom layers. The absorptance of the Au layer reaches its maximum at a thickness of 4.75 nm and decreases due to increased reflectance as the thickness is further increased. The arrows show the trend with increasing Au film thickness. That is, FIG. 9 shows how τ decreases as well as how R increases above the plasmon frequency (about 580 nm) with increasing Au thickness. Interestingly, α increases up to 4.75 nm of Au, where the absorptance reaches a flat broadband behavior in the NIR. Further increasing the thickness of the Au film decreases α due to increased R (optically thick, metallic behavior), as indicated by the arrows in FIG. 9.
[0143] The percolation limit is further confirmed using a scanning electron microscope (SEM, Hitachi SU8230). In FIG. 10, scanning electron microscope images of different thicknesses of Au are shown. In these SEM images, the thickness parameters are 2 nm, 3 nm, 4.75 nm, and 7 nm. Below the percolation threshold (2 nm and 3 nm), the Au nanoparticles form single unconnected islands. At 4.75 nm, interconnection between individual clusters is achieved; i.e., at the threshold (4.75 nm), the islands are interconnected. Above the threshold (7 nm), Au starts to form a continuous layer. Scale bar (A), (B), (C), (D): 100 nm.
[0144] Furthermore, the electrical resistance R of the Au layer with different Au thickness parameters el To determine the electrical percolation limit, we also performed four-probe measurements (Jandel Universal Probe Station). -6 A is set to 4.53 x 10 -5 A and 4.53 x 10 -4A while measuring the voltage at different spots on each sample. Figure 11 shows the resistance of the Au layer on a logarithmic scale, where each circled dot represents a data point. In the case of a continuous layer (30 nm of Au), the Au layer is highly conductive (metallic) and the electrical resistance increases towards the percolation threshold until it becomes an open circuit (dielectric). The thickness parameter d Au = 2 nm, 3 nm, 4 nm, 4.25 nm, and 4.5 nm also R el was measured, but R el increases to infinity, i.e., these films are not conductive. Therefore, the thickness d Au A thin film with electrical resistance R acts as a conductor until it reaches the percolation limit. el is the thickness parameter d Au = 4.75 nm, which indicates dielectric behavior and that the individual Au particles are not electrically connected.
[0145] Furthermore, we quantify the angular dependence of the transmittance of the as-fabricated heater coating (Au thickness parameter of 4.75 nm with TiO2 underlayer and overlayer of thickness parameter of 3 nm) up to an incidence angle of 45°. Figure 12 shows that τ is independent of the incidence angle of the incident light. The distortion between 600 and 900 nm arises due to the change in the diffraction grating of the UV / VIS NIR spectrometer.
[0146] Supplementary Note 3: Contact angle measurement Advancing contact angles for the uncoated substrate (fused silica, SiO2), the control sample (TiO2-coated fused silica), and the metamaterial, i.e., the heater coating.
number
number
number
number
number
number
number
[0147] Sidebar 4: Transient Heat Transfer Model The temperature evolution of a sample with metamaterial, i.e. with a heater coating on top, under solar illumination is estimated using a transient heat transfer model:
number
[0148] Here, m is the mass and c(=750 JkgK -1 ) is the specific heat capacity, and T s is the sample temperature, A is the surface area of the sample (22 × 22 mm),
number
[57] , an assumption that will be verified later by experiments (see below). This allows us to define the Biot number across the thickness of the substrate as
number
[0149] The term on the left hand side of equation (S7) represents the rate of change of the internal energy of the sample, while the right hand side of the equation contains a term for the absorbed solar heat, plus re-radiation to the surroundings and convection heat losses. The temperature rise of the sample above the ambient temperature is less than 10°C, i.e., dT = (T s,eq -T amb )< <T amb Therefore, we linearize the radiative heat transfer term using a Taylor series expansion and eliminate all higher order terms, and obtain T sBy solving equation (S7), the transient sample temperature is derived:
number
number
number
[0150] Experience-based conv To verify the initial guess of h, we used a lumped heat capacity model. conv To this end, the sample is s is in steady state (T s =T s,eq ), the sample is first illuminated by sunlight until it reaches a temperature of 0.25° C. Then, with the solar simulator turned off, the temperature decay of the sample is recorded over three experimental runs, from which an average value is determined. For these experiments, the solar heating term in equation (S7) vanishes, so the solution simplifies to:
number
[0151] Equation (S9) is conv (and thus C2) allows fitting of experimental data to the measured temperature decay. conv ≒9.15Wm -2 K -1 We find the best fit to , which validates our initial guess. Therefore, the experimental data of the temperature rise of the sample under solar illumination in Figure 2 (8.5 ≤ h conv ≦10.5Wm -2 K -1 ) is used as a premise for fitting the model.
[0152] Supplementary Note 5: Defogging behavior FIG. 14 further illustrates the haze elimination behavior of the control sample and the haze elimination behavior of the coating.
[0153] FIG. 14A shows an exemplary result of the time evolution of the haze fraction f, where the heater coating on the SiO2 substrate and the control sample are illuminated at 1 sun (see Methods for experimental procedure and binarization). As can be seen in FIG. 14A, the onset of haze elimination starts much earlier in the case of the metamaterial, i.e., heater-coated sample, due to the higher surface temperature. That is, the experimental results show that the haze fraction f for the heater coating on the SiO2 substrate decreases much more quickly than the haze fraction f for the control sample.
[0154] FIG. 14B shows the qualitative behavior (i.e., recorded frames) by image sequences viewed from above on the cloudy area of two exemplary experimental runs shown in A, at cloud fractions of f=0.75, 0.5, and 0.25, respectively. The dashed rectangle indicates the sample area considered to calculate f. The heater-coated sample requires 107 seconds to defog 75% of the surface, whereas the control sample reaches this value after 342 seconds (more than three times longer). That is, the defog front moves similarly for the heater-coated and control samples on a SiO2 substrate, but at significantly different speeds. Both experiments were performed at 1000 Wm -2 , T amb The experiment was carried out under solar illumination at ≈23°C and RH ≈55%.
[0155] FIG. 14C shows the defogging time t d (i.e., the time required to reach f=0.05), showing that the defogging performance of the coating according to the invention is improved by a factor of 2-3 compared to the control sample. Indeed, FIG. 14C shows that the defogging time t d , i.e. the time required for the sample to become less than 5% covered with cloudiness. Scale bar B): 5 mm.
[0156] Appendix 6: Outdoor testing of vision glasses with heating device coating The real-world feasibility of heater-coated vision glasses was tested in different locations and under different conditions. As can be seen in Figure 15, the left lens of the glasses contains a heater coating, while the right lens is uncoated.
[0157] Figure 15A shows a clear autumn day (T amb ≒12℃, RH≒70%, I0=491Wm -2 FIG. 15B shows images of the first experiment on the terrace of a building on a sunny winter day (T ≈ 0.5 sun). amb ≒4℃, RH≒46%, I0≒339Wm -2 ≈0.5 sun), and visualizes how well it prevents fogging compared to an uncoated lens. amb ≒4℃, RH≒80%, I0≒212Wm -2 We show how this effect is evident even at low temperatures (≒0.5 suns).
[0158] Furthermore, the photothermal performance of the vision glasses according to the invention was evaluated by outdoor experiments (see FIG. 16). For this purpose, on a sunny autumn day, the temperature of both lenses was recorded for one hour using a T-type thermocouple (Omega HSRTC-TT-T-36-36) connected to a thermocouple logger (Lutron TM-947SD). Furthermore, the global horizontal irradiance (I0) was accessed during the experiment (obtained from MeteoSwiss, Kipp&Zonen pyranometer, CM21).
[0159] FIG. 16A shows a photograph of the experimental setup, and FIG. 16B shows the temperature progression of an uncoated lens (control, dark grey) and a lens coated with a heating device (light grey). The global solar irradiance I0 is also shown. The coating consistently increases the temperature of the lens compared to the uncoated lens; that is, FIG. 16B shows that I0 ≈ 525 Wm -2 (corresponding to approximately 0.53 suns), indicating that the heating device coated lens has a consistently higher temperature than the uncoated lens. Scale bar A): 2 cm.
[0160] Therefore, even under realistic outdoor conditions, the heating device can reduce the T s is the T of an uncoated lens. s Consistently higher than.
[0161] Appendix 7: Heating Device Coatings on Flexible and Portable Substrates The optical properties of the ultrathin (~10 nm) heating device when deposited on a compliant substrate (overhead projector transparency sheet, A4, folex®) were tested. The substrate was segmented into 7x7 cm square pieces on which the coating was deposited. The sample was then further segmented into 3.5x3.5 cm squares and the transmittance τ and reflectance R (UV / VIS NIR spectrometer, Jasco, V770) were measured at normal incidence using an ILN-925 integrating sphere and the absorptance was calculated as α=1-τ-R.
[0162] For this purpose, first all properties of the unbent flat sample were measured, the results of which are shown in FIG. 17A. FIG. 17A shows the transmittance τ and absorptance α of the coated substrate (overhead projector transparency) before (solid line) and after (dashed line) 300 bending cycles. The transmittance for the curved sample is also shown. Obviously, as shown in FIG. 17A, the optical properties of the foil with heater coating are not affected by the bending action. Due to the ultra-thin dimensions and porous nature of this foil with heater coating, the much larger radius of curvature of the bending process does not cause mechanical damage to the coating. Furthermore, the optical properties of the coating are not affected, because the scale of the random arrangement of the photothermal material (a few hundred nm) is also much smaller than the bending radius of curvature. Therefore, the heater coating can be deposited on any portable, flexible / foldable material and can be retroactively applied on different transparent surfaces such as windows, displays, or eyewear.
[0163] Next, τ is determined for the sample bent at 40°. Figure 17B shows an image of the bent sample (40°) shown in Figure 17A. Finally, the sample is folded manually 300 times consecutively so that the two ends of the substrate touch each other each time (Figure 17C) and the optical properties are measured again. That is, the photo shown in Figure 17C shows the fully bent sample during the bending cycle. The sample was folded manually 300 times and its optical properties were measured again (see Figure 17A).
[0164] Furthermore, it was possible to demonstrate the usefulness of the heating device as a portable defogging foil. A piece of overhead projector transparency coated with the heating device was taped onto a fused silica wafer. The wafer with the coating was then heated to a temperature of I0 ≈ 100-200 Wm. -2The wafer was exposed to sunlight in the Swiss Alps for 2 min with an irradiance of 10 ... -2 ) Scale bars B), C): 5mm, D): 2cm.
[0165] FIG. 18A shows a cross-sectional rendering of the coating and shows a gold photothermal element consisting of a percolation structure substantially at the percolation threshold, embedded between two dielectric elements made of TiO2 on a substrate (SiO2). FIG. 18B shows a scanning transmission electron microscope image (top) and energy dispersive X-ray spectroscopy mapping (bottom) of the heating device. The actual Au thickness is (d Au = 4.75 nm). The gold photothermal material (dark grey) is placed on a SiO2 substrate. TiO2 = 3 nm thickness). Scale bar B): 10 nm. The actual Au thickness is encapsulated between two TiO2 layers of about 2-3 nm (with a thickness parameter of d = 3 nm). Scale bar B): 10 nm. Au = 4.75 nm). The Au layer (dark gray) forming the percolation is on the SiO2 substrate (nominal d TiO2 = 3 nm) between two TiO2 layers of about 2-3 nm. Scale bar B): 10 nm. Figure 18C shows the angular dispersion relationship of the absorptance for radiation incidence angles θ up to 30° relative to the normal to the heating device, demonstrating that the absorptance is preserved for oblique illumination.
[0166] 19A and 19B are graphs showing the broadband absorptance in the near infrared spectrum of a heating device including a photothermal element in the form of gold. As can be seen from FIG. 19A, the broadband absorptance in the near infrared spectrum increases above the percolation threshold (thickness parameter d Au = 4.75 nm), which makes the heating device robust to small manufacturing errors. FIG. 19B shows the absorption spectra of a heating device including a photothermal element in the form of gold with and without an upper dielectric shift element made of (TiO2) on top. As can be seen from these spectra, the heating device including a photothermal element made of a layer of Au embedded in a lower dielectric element (TiO2) and an upper dielectric shift element (TiO2) shows a larger α, which shifts the minimum wavelength of the range of interest towards smaller wavelengths as described above.
[0167] FIG. 20A shows a bright-field SEM image of a heating device that includes a photothermal structure at the percolation threshold embedded between two dielectric elements. The photothermal material is Au (black) and is uniformly surrounded by the dielectric elements (TiO2 layer, dark grey). The SiO2 substrate is at the bottom, whereas the top is covered with carbon to facilitate imaging (both light grey). FIG. 20B shows high-resolution transmission electron microscopy. The actual thickness (d Au = 4.75 nm), TiO2 is about 2 to 3 nm (d TiO2 = 3 nm thickness parameter), is estimated to be about 6-7 nm. The overall roughness of the structure remains within a few nm, and the photothermal element (Au layer) is fully embedded between the dielectric elements (TiO2 on both sides).
[0168] FIG. 21 shows the angular dependence of the optical properties of the heating device described above. Incident radiation measurements are performed at an angle θ relative to the normal to the heating device. The measured transmittance and reflectance are displayed in the top and middle panels, respectively. From these the absorptance is estimated and shown in the bottom panel. As the heating device is much thinner than the corresponding incident wavelength, it exhibits little angular dispersion in both its transmittance and reflectance. As a result, the absorptance is nearly constant between 800 and 2000 nm and between θ=0 and 30°.
[0169] FIG. 22 shows a comparison of the heating device according to the present invention described above with a prior art photothermal anti-fog coating as a function of visible transparency τ VIS and the solar absorption per unit thickness d (unit: nm) of the material, α solar It is shown as a function of α solar Values for are obtained based on text values given in the source or, if not directly available, by direct extraction from drawings followed by numerical integration and convolution with the AM1.5Global (ASTMG173) solar reference spectrum. In cases where data for absorbance or transparency are missing, reflectance is assumed to be zero, thus favoring the prior art. For thickness, values are obtained from the text where possible. In cases where the overall thickness was not reported, the overall thickness was estimated from cross-sectional SEM images provided or from a combination of implications of the paper.
[0170] Figure 23 shows photothermal results at low levels of solar irradiance. Box plots (n=5) of steady-state temperature rise of the heating device according to the invention and the control sample under different levels of solar irradiance I0 including 0.2 sun and 0.4 sun show the effectiveness of the heating device according to the invention even at low I0. The box plot includes a center line, upper and lower quartiles, and whiskers (1.5 times the interquartile range). Both plots show the sample temperature T sThe temperature rise of the heating device at 0.2 sun and the control sample (see above for details) was measured. Figure 23 shows that the heating device strongly outperforms the control even at such low levels of solar irradiance. At 0.2 sun, the control shows an average temperature rise of 0.36°C, while the coating reaches a temperature rise of 2.2°C. At 0.4 sun, the control warms up by only 0.41°C, while the heating device warms up by 1.2°C. s A steady state temperature of 3.7°C above the
[0171] Figures 24A and 24B show outdoor testing of the heating device with a pair of prescription glasses. Thermal performance tests were conducted on an overcast day, showing that the heating device works efficiently even under cloudy and windy conditions. Both the temperature of the uncoated lens (control, grey) and the temperature of the lens coated with the heating device according to the invention were recorded. The solar irradiance I0 is also shown. The temperature of both lenses was recorded using a T-type thermocouple (Omega HSRTC-TT-T-36-36) connected to a thermocouple logger (Lutron TM-947SD). In addition, the global horizontal irradiance (I0) was accessed during the experimental run (obtained from MeteoSwiss, Kipp&Zonen pyranometer, CM21). Figures 25A and 25B show indoor testing of the heating device according to the invention placed on a pair of prescription glasses placed behind a triple-glazed window. Both the temperature of the uncoated lens (control, grey) and the temperature of the lens coated with the heating device according to the invention were recorded. The solar irradiance I0 is also shown. Even though the window glass strongly reduces the transmitted solar energy, the heating device according to the invention still outperforms the control even at low levels of I0. I0 is recorded using a thermal power sensor (Thorlabs S425C and PM100 USB controller).
[0172] Figure 26 shows the performance of the heating device according to the invention disposed on different polymer substrates. In particular, the heating device was deposited on polystyrene (PS), polycarbonate (PC), acrylic glass (PMMA) apart from the deposition on SiO2 and polyester mentioned above. These substrates were exposed to oxygen plasma for 2 minutes before deposition (Oxford Instrument, Plasmalab 80 Plus). As these substrates are essentially smooth, atomic force microscopy was used to characterize the roughness of all surfaces. The root mean square (RMS) roughness of PC is 4.56 nm, the root mean square roughness of PMMA is 10.83 nm and the root mean square roughness of PS is 17.78 nm. These values represent the RMS roughness over a spot size of 20x20 μm, whereas RMS roughness values over a local area of the substrate (0.9x0.9 μm) may be higher (i.e., 17.20 nm was measured for PC and 52.80 nm for PMMA). Panel A) shows the absorption α of the bare polymer (grey) and the substrate on which the heating device was coated, confirming that the heating device comprises a photothermal material consisting of a percolation structure at or substantially at the percolation threshold. Panel B) shows an SEM micrograph of the as-fabricated heating device (without a TiO2 overlayer for ease of imaging), further confirming that the photothermal material consists of a percolation structure at or substantially at the percolation threshold.
[0173] Figures 27A and 27B show heat resistance and abrasion resistance tests. To evaluate the effect of repeated long-term heating on the optical properties of the heating device and therefore on its photothermal performance, the heating device is repeatedly heated (about 1 sun irradiance) and cooled for 50 cycles. The heating device used in all experiments was manufactured more than 6 months ago and was stored under ambient air for the entire period before the experiment. Figure 27A shows the T for 50 cycles under about 1 sun exposure. sFigure 27B shows the absorbency α before (grey) and after (dark grey) 50 temperature cycles, demonstrating no degradation in performance.
[0174] 27C and 27D show a heat resistance test in which the heating device was exposed to an irradiance of about 1 sun for 63 hours and the absorbance was measured before and after. C) T amb Exceeding T s D) Absorbance α before (gray) and after (dark grey) a 63-hour sun exposure experiment.
[0175] 27E and 27F show abrasion resistance tests, in which the permeability τ of the heating device is measured before and after E) a peel test and F) a wipe test. In the peel test (according to ASTM D3330 standard / method A), a pressure-sensitive tape (3M™ VHB™) is firmly attached to the heating device and is peeled off at an angle of 180°, i.e. parallel to the heating device. In the wipe test, the heating device is wiped with a microfiber cloth under realistic pressure 50 times (according to DIN 30643). As can be seen, the heating device according to the invention retains its optical properties after both abrasion tests.
[0176] Figures 27G and 27H show abrasion resistance tests, in which the permeability τ of the heating device is measured before and after G) abrasion resistance test by ablation and H) abrasion resistance test by falling sand. In the ablation test (according to standard test method ASTM F735-94), the heating device is placed in a small dish and covered with quartz sand (grain size 0.1-0.8 mm). It is placed on a mixer (heidolph Multi Reax) and shaken at 1000 rpm for 1 minute. The falling sand test (according to ASTM F735-94) evaluates the impact resistance of the heating device. Quartz sand (grain size 0.1-0.8 mm) falls through a tube (inner diameter 5 cm) through a mesh (mesh width of about 1.5 mm) onto the coating. The fall height is 35-40 cm. As can be seen, the heating device according to the invention retains its optical properties after both abrasion tests. [Explanation of symbols]
[0177] 1 Heating device 2. Light and heat elements 3. Electrical elements 4 Dielectric Elements 5 Shifting factors 6. Anti-reflective elements 7. Carrier Elements 8 Top side E Extending direction T Horizontal
Claims
1. A heating device (1) for preventing or removing deposits, in particular for dew elimination, dew prevention, deicing or anti-icing, comprising: The heating device (1) extends along an extension direction (E) and comprises at least one photothermal element (2) configured to exhibit a photothermal effect when electromagnetic radiation is incident thereon, The photothermal element (2) comprises or consists of a photothermal material including a percolation structure; The heating device (1), characterized in that the percolation structure is at or substantially at its percolation threshold.
2. the photothermal material is optically transparent, the photothermal material being optically transparent to electromagnetic radiation, preferably in the visible region of the electromagnetic spectrum; and / or 2. The heating device (1) of claim 1, wherein the photothermal material is configured to absorb incident electromagnetic radiation, the photothermal material being preferably configured to absorb incident electromagnetic radiation in the near infrared region of the electromagnetic spectrum.
3. the photothermal element is electrically conductive or electrically insulating; and / or 3. The heating device (1) according to claim 1 or 2, further comprising at least one electric element (3) configured to induce an electric current in the photothermal element (2), whereby heat is generated by the photothermal element (2), the electric element (3) being preferably an electrode.
4. said photothermal element (2) has a thickness in the range of 1 nm to 50 nm, preferably in the range of 1 nm to 10 nm, with respect to said extension direction (E); and / or the heating device (1) has a thickness in the range of 1 nm to 100 nm in the extension direction (E); and / or The heating device (1) according to any one of claims 1 to 3, wherein the photothermal element (2) and / or the heating device (1) have a thickness, in the extension direction (E), that is significantly smaller than the wavelengths in the visible range and the near infrared range of the incident electromagnetic radiation.
5. the heating device is bendable; and / or The heating device (1) according to any one of claims 1 to 4, wherein the heating device (1) when bent includes an inverse curvature of more than 1 μm.
6. The heating device (1) according to any one of claims 1 to 5, wherein the light-heating element (2) is a layer, the layer preferably extending along a transverse direction (T) extending perpendicularly to the extension direction (E).
7. The photothermal material is electrically conductive and / or comprises or consists of at least one metal such as gold, silver, aluminum, copper, platinum, or tungsten and / or is a metal or metal alloy; or Heating device (1) according to any one of the preceding claims, wherein the photothermal element is a semiconductor.
8. The heating device (1) further comprises at least one dielectric element (4), the dielectric element (4) being arranged in front of or behind the light-heat element (2) with respect to the extension direction (E), and The dielectric element (4) and the photothermal element (2) are preferably in at least partial surface contact with each other, and / or Heating device (1) according to any one of claims 1 to 7, wherein the dielectric element (4) is preferably optically transparent and / or comprises or consists of at least one metal oxide or metal nitride, preferably titanium dioxide, silicon dioxide, tantalum pentoxide, titanium nitride.
9. the heating device (1) further comprises at least one shift element (5) configured to shift the absorption and / or transmission capacity of the heating device (1) with respect to the incident electromagnetic radiation towards shorter or longer wavelengths of the incident electromagnetic radiation; and / or The heating device (1) according to any one of claims 1 to 8, further comprising at least one anti-reflection element (6) constructed and arranged to reflect electromagnetic radiation towards the photothermal element (2).
10. the shifting element (5) and / or the anti-reflection element (6) are arranged in front of or behind the photothermal element (2) with respect to the extension direction (E); and / or The heating device (1) according to claim 9, wherein the shifting element (5) and / or the anti-reflection element (6) are at least one of transparent and dielectric, and the shifting element (5) preferably comprises or consists of a dielectric element (4) according to claim 8.
11. The heating device (1) further comprises at least one carrier element (7), The photothermal element (2) is arranged on or at least partially embedded in the carrier element (7), The heating device (1) according to any one of claims 1 to 10, wherein the carrier element (7) is preferably at least one of bendable, flexible, deformable, foldable, optically transparent and / or comprises or consists of a solid, preferably an amorphous solid such as glass, and / or one or more plastics and / or one or more polymers, preferably transparent and / or elastic plastics or polymers.
12. A method for manufacturing a heating device (1) for preventing or removing deposits, in particular for condensation removal, dew prevention, ice removal or ice prevention, comprising the steps of: The heating device (1) extends along an extension direction (E) and preferably corresponds to a heating device (1) according to any one of claims 1 to 11, The method comprises: Providing at least one photothermal element (2) configured to exhibit a photothermal effect when electromagnetic radiation is incident thereon. Including, The photothermal element (2) comprises or consists of a photothermal material including a percolation structure; The method of claim 1, wherein the percolation structure is at or substantially at its percolation threshold.
13. 13. The method according to claim 12, wherein the photothermal element (2) is produced by deposition, preferably by thin film deposition and / or vapor phase deposition and / or by chemical growth, the photothermal element (2) being particularly preferably produced by island growth.
14. Method according to claim 12 or 13, wherein the photothermal element (2) is produced by deposition at a deposition rate in the range of 0.05 nm / s to 1 nm / s and / or during a deposition time in the range of 1 s to 150 s.
15. The photothermal element (2) is produced directly on a dielectric element (4), a shift element (5) or a carrier element (7), and / or Method according to any of claims 12 to 14, wherein said photothermal element (2) is preferably produced by direct deposition of at least one electrically conductive material.